Magnetic recording medium, magnetic tape cartridge, and magnetic recording / reproducing device

By designing non-magnetic and magnetic layers with specific content and structure in magnetic recording media, the problem of degradation of magnetoelectric conversion characteristics after the medium is stored in high temperature and high humidity environments is solved, and performance stability and durability are achieved.

JP2025057156APending Publication Date: 2025-04-09FUJIFILM CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023166843
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-28
Publication Date
2025-04-09

AI Technical Summary

Technical Problem

The problem of deterioration of magnetoelectric conversion characteristics after existing magnetic recording media is stored in high temperature and high humidity environments.

Method used

A magnetic recording medium with a non-magnetic support layer, a magnetic layer and a non-magnetic layer is used, wherein the total chlorine content and iron content of the magnetic layer and the non-magnetic layer are within a specific range, the porosity of the non-magnetic layer is less than 10%, and contains at least 50% carbon black in the non-magnetic layer.

Benefits of technology

It effectively suppresses the deterioration of magnetoelectric conversion characteristics and ensures stable performance of the medium after storage under harsh conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025057156000001
    Figure 2025057156000001
  • Figure 2025057156000002
    Figure 2025057156000002
  • Figure 2025057156000003
    Figure 2025057156000003
Patent Text Reader

Abstract

To provide a magnetic recording medium having a magnetic layer and a non-magnetic layer, in which deterioration of electromagnetic conversion characteristics after storage under hard conditions is small.SOLUTION: A magnetic recording medium has a non-magnetic support body and a magnetic layer containing ferromagnetic powder, and further has a non-magnetic layer containing non-magnetic powder between the non-magnetic support body and the magnetic layer, in which the total chlorine content of the magnetic layer and the non-magnetic layer is 30.0 mg / m2 or less per unit area and the total iron content of the magnetic layer and the non-magnetic layer is 300.0 mg / m2 or less per unit area. A magnetic tape cartridge and a magnetic recording / reproducing device include this magnetic recording medium.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a magnetic recording medium, a magnetic tape cartridge, and a magnetic recording / reproducing device. [Background technology]

[0002] 2. Description of the Related Art Known magnetic recording media include a magnetic layer and a non-magnetic layer (see, for example, Patent Documents 1 to 3). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2020-144960 A [Patent Document 2] JP 2004-103067 A [Patent Document 3] JP 2005-267714 A Summary of the Invention [Problem to be solved by the invention]

[0004] Desirable performance of a magnetic recording medium is excellent electromagnetic conversion characteristics. Regarding electromagnetic conversion characteristics, for example, JP 2020-144960 A (Patent Document 1) describes that the magnetic tape of the embodiment showed little deterioration in electromagnetic conversion characteristics after repeated running under an environment of a temperature of 23°C and a relative humidity of 45% (see paragraphs 0119, Table 1, and paragraph 0123 of JP 2020-144960 A (Patent Document 1)). In response to this, the present inventor considered that in the future, magnetic recording media are expected to be used after being stored under harsh conditions (for example, in a high-temperature environment, in a high-humidity environment, and / or for a long period of time).

[0005] Therefore, an object of one aspect of the present invention is to provide a magnetic recording medium having a magnetic layer and a non-magnetic layer, which exhibits little deterioration in electromagnetic conversion characteristics after storage under harsh conditions. [Means for solving the problem]

[0006] One aspect of the present invention is as follows. [1] A magnetic recording medium having a non-magnetic support and a magnetic layer containing a ferromagnetic powder, a non-magnetic layer containing a non-magnetic powder between the non-magnetic support and the magnetic layer, The total chlorine content of the magnetic layer and the non-magnetic layer is 30.0 mg / m 2 is less than or equal to, and The total iron content of the magnetic layer and the non-magnetic layer is 300.0 mg / m 2 1. A magnetic recording medium comprising: [2] The magnetic recording medium according to [1], wherein in a cross-sectional image taken by a scanning electron microscope, the nonmagnetic layer has a void ratio of 10.0% or less. [3] The magnetic recording medium according to [1] or [2], wherein the nonmagnetic powder in the nonmagnetic layer contains carbon black. [4] The magnetic recording medium according to [3], wherein the nonmagnetic layer contains 50.0% by mass or more of carbon black based on the total amount of the nonmagnetic powder. [5] The magnetic recording medium according to any one of [1] to [4], wherein the nonmagnetic layer has a thickness of 1.00 μm or less. [6] The magnetic recording medium according to any one of [1] to [5], further comprising a backcoat layer containing a nonmagnetic powder on the surface side of the nonmagnetic support opposite to the surface side having the nonmagnetic layer and the magnetic layer. [7] The magnetic recording medium according to any one of [1] to [6], which is a magnetic tape. [8] In a cross-sectional image taken by a scanning electron microscope, the void ratio of the nonmagnetic layer is 10.0% or less; the non-magnetic layer contains 50.0% by mass or more of carbon black based on the total amount of the non-magnetic powder, The nonmagnetic layer has a thickness of 1.00 μm or less, a backcoat layer containing a nonmagnetic powder on the surface side of the nonmagnetic support opposite to the surface side having the nonmagnetic layer and the magnetic layer; and The magnetic recording medium according to [1], which is a magnetic tape. [9] A magnetic tape cartridge comprising the magnetic tape described in [7] or [8].

[10] A magnetic recording and reproducing device comprising the magnetic recording medium according to any one of [1] to [8]. Effect of the Invention

[0007] According to one aspect of the present invention, it is possible to provide a magnetic recording medium having a magnetic layer and a non-magnetic layer, and exhibiting little deterioration in electromagnetic conversion characteristics after storage under harsh conditions. Also, according to one aspect of the present invention, it is possible to provide a magnetic tape cartridge and a magnetic recording and reproducing device including such a magnetic recording medium. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] [Magnetic recording media] One aspect of the present invention relates to a magnetic recording medium having a non-magnetic support and a magnetic layer containing ferromagnetic powder, and further having a non-magnetic layer containing non-magnetic powder between the non-magnetic support and the magnetic layer. The total chlorine content of the magnetic layer and the non-magnetic layer is 30.0 mg / m2 as a value per unit area (hereinafter also referred to as "chlorine content (magnetic layer + non-magnetic layer)"). 2 and the total iron content of the magnetic layer and the non-magnetic layer is 300.0 mg / m or less in terms of the value per unit area (hereinafter also referred to as "iron content (magnetic layer + non-magnetic layer)"). 2 The following is the result.

[0009] <Method of measuring chlorine content (magnetic layer + non-magnetic layer) and iron content (magnetic layer + non-magnetic layer)> In the present invention and this specification, the above-mentioned "chlorine content (magnetic layer+nonmagnetic layer)" and the above-mentioned "iron content (magnetic layer+nonmagnetic layer)" are determined by the following method. (1) A sample piece for measurement is cut out from the magnetic recording medium to be measured. The size of the sample piece may be any size that can be introduced into an X-ray fluorescence analyzer. (2) The cut sample pieces are introduced into an X-ray fluorescence analyzer, and the amount of chlorine (Cl) is measured from the peak area of ​​the chlorine (Cl) element, and the amount of iron (Fe) is measured from the peak area of ​​the iron (Fe) element. (3) After the measurement in (2) above, the sample piece is removed from the X-ray fluorescence analyzer, and the magnetic layer and the non-magnetic layer are wiped off and removed with a solvent. The solvent used here may be any solvent capable of removing the magnetic layer and the non-magnetic layer. The sample piece is then introduced into the X-ray fluorescence analyzer, and the amount of Cl is measured from the peak area of ​​the Cl element, and the amount of Fe is measured from the peak area of ​​the Fe element. In this way, for a magnetic recording medium having a backcoat layer, the total amount of Cl and the total amount of Fe in the backcoat layer and the non-magnetic support are obtained. For a magnetic recording medium not having a backcoat layer, the amount of Cl and the amount of Fe in the non-magnetic support are obtained. (4) Calculate the "chlorine content (magnetic layer + nonmagnetic layer)" and "iron content (magnetic layer + nonmagnetic layer)" using the following formula. Chlorine content (magnetic layer + non-magnetic layer) (mg / m 2 ) = [amount of Cl determined in (2) above - amount of Cl determined in (3) above] / area of ​​sample piece Iron content (magnetic layer + non-magnetic layer) (mg / m 2 )=[Fe content determined in (2) above−Fe content determined in (3) above] / area of ​​sample piece

[0010] The present inventors have conducted extensive research to provide a magnetic recording medium having a magnetic layer and a non-magnetic layer, which exhibits little deterioration in electromagnetic conversion characteristics after storage under harsh conditions. As a result, the inventors have newly discovered that a magnetic recording medium in which the chlorine content (magnetic layer + non-magnetic layer) and the iron content (magnetic layer + non-magnetic layer) are within the ranges described above can suppress deterioration in electromagnetic conversion characteristics after storage under harsh conditions. In this regard, the inventors speculate that the chlorine element and the iron element contained in the magnetic layer and / or the non-magnetic layer may cause deterioration in the magnetic properties of the ferromagnetic powder contained in the magnetic layer, film deterioration of the magnetic layer, and / or film deterioration of the non-magnetic layer during storage under harsh conditions. In contrast, the present inventors believe that a magnetic recording medium in which the chlorine content (magnetic layer + non-magnetic layer) and the iron content (magnetic layer + non-magnetic layer) are within the ranges described above can suppress the occurrence of such deterioration, and as a result, it is possible to suppress deterioration in electromagnetic conversion characteristics after storage under harsh conditions. However, the present invention is not limited to the speculations described in this specification. In contrast, the previously mentioned JP 2020-144960 A (Patent Document 1), JP 2004-103067 A (Patent Document 2), and JP 2005-267714 A (Patent Document 3) do not suggest that either the chlorine content (magnetic layer + non-magnetic layer) or the iron content (magnetic layer + non-magnetic layer) should be reduced.

[0011] <Chlorine content (magnetic layer + non-magnetic layer)> The chlorine content of the above magnetic recording medium (magnetic layer + non-magnetic layer) is set to 30.0 mg / m from the viewpoint of suppressing deterioration of electromagnetic conversion characteristics after storage under harsh conditions. 2 ≤ 28.0 mg / m 2 Preferably, it is 25.0 mg / m or less. 2 Below, 20.0mg / m 2 Below 15.0mg / m 2 Below, 10.0mg / m 2 The chlorine content of the magnetic recording medium (magnetic layer + non-magnetic layer) is preferably, for example, 0.0 mg / m 2 More than 0.0mg / m 2 Ultra, 1.0mg / m 2 More than 2.0mg / m 2More than 3.0mg / m 2 More than 4.0mg / m 2 or 5.0 mg / m 2 The smaller the chlorine content (magnetic layer+non-magnetic layer) of the magnetic recording medium, the more preferable it is from the viewpoint of suppressing deterioration of the electromagnetic conversion characteristics after storage under harsh conditions.

[0012] <Iron content (magnetic layer + non-magnetic layer)> The iron content of the magnetic recording medium (magnetic layer + non-magnetic layer) is set to 300.0 mg / m from the viewpoint of suppressing deterioration of electromagnetic conversion characteristics after storage under harsh conditions. 2 Less than or equal to 280.0 mg / m 2 It is preferable that the concentration is 250.0 mg / m or less. 2 Below 200.0mg / m 2 Below, 150.0mg / m 2 Below, 100.0mg / m 2 The iron content of the magnetic recording medium (magnetic layer + non-magnetic layer) is preferably, for example, 0.0 mg / m 2 More than 0.0mg / m 2 Ultra, 1.0mg / m 2 More than 5.0mg / m 2 More than 10.0mg / m 2 More than 20.0mg / m 2 More than 30.0mg / m 2 More than 40.0mg / m 2 More than 50.0mg / m 2 More than 60.0mg / m 2 More than 70.0mg / m 2 More than 80.0mg / m 2 or more than 90.0 mg / m 2 The iron content (magnetic layer+non-magnetic layer) of the magnetic recording medium is preferably as low as possible, from the viewpoint of suppressing deterioration of the electromagnetic conversion characteristics after storage under harsh conditions.

[0013] The above magnetic recording medium will now be described in more detail.

[0014] <Thickness of each layer and non-magnetic support> The magnetic recording medium has the nonmagnetic layer and the magnetic layer, and in one embodiment, may further have a backcoat layer containing a nonmagnetic powder on the surface side of the nonmagnetic support opposite to the surface side having the nonmagnetic layer and the magnetic layer. In another embodiment, the magnetic recording medium may be a magnetic recording medium without such a backcoat layer. The thickness of the magnetic layer can be optimized according to the saturation magnetization amount of the magnetic head used, the head gap length, the band of the recording signal, etc. The thickness of the magnetic layer is preferably 100 nm or less from the viewpoint of high density recording, more preferably 10 to 100 nm, and even more preferably 20 to 90 nm. There is at least one magnetic layer, and the magnetic layer may be separated into two or more layers having different magnetic properties, and a known configuration related to a multilayer magnetic layer can be applied. The thickness of the magnetic layer when separated into two or more layers is the total thickness of these layers. This also applies to the case where other layers are separated into two or more layers. From the viewpoint of increasing the capacity of the magnetic recording medium, the thickness of the nonmagnetic layer is preferably 1.00 μm or less, more preferably 0.80 μm or less, and more preferably 0.60 μm or less. From the viewpoint of easiness of uniformly applying the composition for forming the nonmagnetic layer, the thickness of the nonmagnetic layer is preferably 0.05 μm or more, more preferably 0.07 μm or more, and even more preferably 0.10 μm or more. In general, the nonmagnetic layer can be a layer thicker than the magnetic layer (for example, the thickness of the nonmagnetic layer can be 2 times or more, 3 times or more, 4 times or more, or 5 times or more than the thickness of the magnetic layer). Therefore, it can be said that the contribution of the magnetic layer components to the chlorine content (magnetic layer + nonmagnetic layer) and the iron content (magnetic layer + nonmagnetic layer) is negligibly small. The thickness of the backcoat layer is preferably 0.90 μm or less, and more preferably in the range of 0.10 to 0.70 μm. The thickness of the nonmagnetic support is, for example, in the range of 2.0 to 80.0 μm, preferably in the range of 2.0 to 50.0 μm, and more preferably in the range of 2.0 to 10.0 μm.

[0015] <Nonmagnetic layer> (Porosity of non-magnetic layer) From the viewpoint of improving the electromagnetic conversion characteristics by increasing the saturation magnetic flux density Bm of the magnetic layer, the void ratio of the non-magnetic layer of the magnetic recording medium is preferably 20.0% or less, more preferably 19.0% or less, 18.0% or less, 17.0% or less, 16.0% or less, 15.0% or less, 14.0% or less, 13.0% or less, 12.0% or less, 11.0% or less, 10.0% or less, 9.0% or less, 8.0% or less, 7.0% or less, 6.0% or less, and 5.0% or less. Also, from the viewpoint of moldability in, for example, calendering, the void ratio of the non-magnetic layer is preferably 0.8% or more, more preferably 1.0% or more, even more preferably 1.2% or more, even more preferably 1.5% or more, and even more preferably 2.0% or more.

[0016] The inventors speculate as follows about the reason why it is possible to increase the saturation magnetic flux density Bm of the magnetic layer by reducing the void ratio of the nonmagnetic layer. The composition for forming the nonmagnetic layer usually contains a binder. It is desirable to adsorb the binder to the particle surface of the nonmagnetic powder as much as possible from the viewpoint of improving the dispersibility of the nonmagnetic powder in the nonmagnetic layer and improving the film strength of the nonmagnetic layer, but it is generally believed that the entire amount is not adsorbed. Therefore, it is presumed that the non-adsorbed binder component that can be released is present in the nonmagnetic layer in a mixed state with the adsorbed binder component. It is presumed that the non-adsorbed binder component of this nonmagnetic layer penetrates into the magnetic layer through the gap between the nonmagnetic powder and the adsorbed binder component during the manufacturing process of the magnetic recording medium. If the nonmagnetic component of the magnetic layer increases as a result, the ratio of the ferromagnetic powder to the volume of the magnetic layer decreases. It is presumed that this causes the saturation magnetic flux density Bm of the magnetic layer to decrease. Therefore, the inventor believes that if the porosity of the nonmagnetic layer is reduced, the saturation magnetic flux density Bm of the magnetic layer can be increased as a result.

[0017] In the present invention and this specification, the porosity of the nonmagnetic layer is a value determined from a cross-sectional image obtained using a scanning electron microscope (SEM). A method for determining the porosity of the nonmagnetic layer will be described below.

[0018] (1) Preparation of specimens for cross-sectional observation A sample for cross-section observation is cut out from a randomly determined position of the magnetic recording medium to be measured. The sample for cross-section observation is prepared by implanting gallium ions (Ga + This is done by FIB (Focused Ion Beam) processing using a focused ion beam. A specific example of such a fabrication method is as follows. (i) A sample of magnetic recording medium measuring 10 mm in width direction and 10 mm in length direction is cut out using a razor. A protective film is formed on the surface of the magnetic layer of the cut sample to obtain a sample with a protective film. The protective film is formed by the following method. A platinum (Pt) film (thickness: 30 nm) is formed on the surface of the magnetic layer of the above sample by sputtering. The platinum film is sputtered under the following conditions. (Platinum film sputtering conditions) Target: Pt Vacuum level in the sputtering chamber: 7 Pa or less Current value: 15mA A carbon film having a thickness of 100 to 150 nm is further formed on the platinum film-attached sample prepared above. The carbon film is formed by using a gallium ion (Ga + This is done using a CVD (chemical vapor deposition) mechanism that uses a . (ii) The sample with the protective film prepared in (i) above is irradiated with gallium ions (Ga + The cross section of the magnetic recording medium is exposed by FIB processing using a 30 kV accelerating voltage and 1300 pA probe current in the FIB processing. For example, the cross-section observation sample thus exposed is used for SEM observation to determine the porosity of the non-magnetic layer and for SEM observation to determine the thickness of the magnetic layer, which will be described later.

[0019] (2) Identification of the non-magnetic layer The prepared cross-sectional observation sample is observed by SEM, and a cross-sectional image (SEM image) is taken. As the scanning electron microscope, a field emission scanning electron microscope (FE (Field Emission)-SEM) is used. For example, FE-SEM S4800 manufactured by Hitachi, Ltd. can be used, and this FE-SEM was used in the examples and comparative examples described later. SEM images are taken of the same cross-sectional observation sample at positions randomly selected except that (i) the areas to be photographed do not overlap, (ii) the outermost surface on the magnetic layer side (magnetic layer surface) is included in the SEM image, and (iii) the entire thickness direction of the cross-sectional observation sample (i.e., the area from the outermost surface on the magnetic layer side to the outermost surface on the other side) is included in the SEM image, or, if the entire thickness direction of the cross-sectional observation sample is not included in the SEM image, the proportion of the photographed portion of the cross-sectional observation sample to the total image area of ​​the SEM image is 80 to 100% on an area basis, obtaining a total of 10 images. The SEM image is a secondary electron image (SE (secondary electron) image) captured at an accelerating voltage of 5 kV, a magnification of 50,000 times, and a resolution of 960 pixels (vertical)×1280 pixels (horizontal). The captured SEM image is imported into WinROOF, an image processing software manufactured by Mitani Shoji Co., Ltd., and a portion of the nonmagnetic layer (measurement area) in the SEM image is selected. In selecting the measurement area, the width of the measurement area is the total width of the captured SEM image. The "width direction" described in relation to the SEM image refers to the width direction of the photographed sample for cross-sectional observation. The width direction of the sample for cross-sectional observation refers to the width direction of the magnetic recording medium from which the sample is cut. The above also applies to the thickness direction. In the thickness direction, the interface between the magnetic layer and the non-magnetic layer is identified by the following method. The SEM image is digitized to create image brightness data in the thickness direction (consisting of three components: thickness direction coordinate, width direction coordinate, and brightness). In the digitization, the SEM image is divided into 1280 parts in the width direction, processed with 8-bit brightness to obtain data of 256 gradations, and the image brightness of each divided coordinate point is converted to a predetermined gradation value. Next, in the obtained image brightness data, the average brightness in the width direction at each coordinate point in the thickness direction (i.e., the average brightness at each coordinate point divided into 1280) is taken as the vertical axis, and the thickness direction coordinate is taken as the horizontal axis to create a brightness curve. The brightness curve is differentiated to create a differential curve, and the coordinate of the boundary between the magnetic layer and the non-magnetic layer is identified from the peak position of the created differential curve. The position on the SEM image that corresponds to the identified coordinate is taken as the interface between the magnetic layer and the non-magnetic layer. If the SEM image includes a non-magnetic support, the interface between the non-magnetic layer and the non-magnetic support is identified. For example, in a coating type magnetic recording medium, the interface between the non-magnetic layer and the non-magnetic support can be clearly recognized compared to the interface between the magnetic layer and the non-magnetic layer. Therefore, the interface between the non-magnetic layer and the non-magnetic support can be identified by visually observing the SEM image. However, it may be identified using a brightness curve as described above. When the SEM image does not include a portion of the non-magnetic support, the entire region from the interface between the identified magnetic layer and the non-magnetic layer (i.e., the surface of the non-magnetic layer) to the thickness direction of the portion of the non-magnetic layer is identified as the non-magnetic layer. On the other hand, when the SEM image includes a portion of the non-magnetic support, the entire region from the interface between the identified magnetic layer and the non-magnetic layer (i.e., the surface of the non-magnetic layer facing the magnetic layer) to the interface between the non-magnetic layer and the non-magnetic support (i.e., the surface of the non-magnetic layer facing the non-magnetic support) is identified as the non-magnetic layer.

[0020] (3) Identifying voids in the non-magnetic layer and calculating the void ratio The measurement area identified as the non-magnetic layer in (2) above is subjected to a sharpening process, which is a function of the image processing software WinROOF manufactured by Mitani Shoji Co., Ltd., and then a noise removal process (4 pixels / 1280 pixels) is performed to emphasize the outline of the voids present in the measurement area. The outline of the voids present in the measurement area is then manually selected, and the outline and the area surrounded by the outline are then binarized using the image processing software. At this time, the binarized area is 25 nm 2 The area below 25 nm is not considered as a void but as noise and is excluded from selection. 2 These areas are identified as voids. Next, the areas of the areas identified as voids are added together to determine the total area of ​​voids. The porosity is calculated using the formula below. The porosity is calculated for each of the 10 images, and the arithmetic average of these is determined to be the porosity of the non-magnetic layer. In the formula below, the units for the total area of ​​voids and the area of ​​the measurement region are nm if they are the same units. 2 Even in μm 2 or other units. Porosity (%) = (total area of ​​voids / area of ​​measurement area) x 100

[0021] Among the voids present in the measurement area, there may be voids that are partly inside the measurement area and other parts outside the measurement area. For such voids, the area of ​​the part of the void that is inside the measurement area is used when calculating the total area of ​​the voids to determine the above porosity, and the area of ​​the part that is outside the measurement area is not included in the calculation of the total area.

[0022] On the other hand, the thickness of the magnetic layer is determined by the following method. The cross-sectional observation sample prepared by the method described in (1) above is observed by SEM, and a cross-sectional image (SEM image) is taken. As the scanning electron microscope, a field emission scanning electron microscope (FE-SEM) is used. For example, FE-SEM S4800 manufactured by Hitachi, Ltd. can be used, and this FE-SEM was used in the examples and comparative examples described later. SEM images are taken at 10 randomly selected locations on the prepared cross-sectional observation sample, so that the SEM images include the entire thickness direction of the nonmagnetic layer, at least a part of the magnetic layer, and at least a part of the nonmagnetic support. In this way, a total of 10 SEM images are obtained. The above SEM images are secondary electron images (SE images) taken at an accelerating voltage of 5 kV, a magnification of 50,000 times, and 960 pixels vertical by 1280 pixels horizontal. The interface between the magnetic layer and the non-magnetic layer is identified by the method described in (2) above. The magnetic layer surface is identified by visual inspection. At one arbitrary position on each SEM image, the distance in the thickness direction between the interface between the magnetic layer and the non-magnetic layer specified by the above method and the surface of the magnetic layer is obtained, and the arithmetic average of the values ​​obtained for 10 images is taken as the thickness of the magnetic layer. The thicknesses of layers other than the magnetic layer and the non-magnetic support can also be determined by the same method. Alternatively, the thicknesses of the other layers may be determined as the design thickness calculated from the manufacturing conditions.

[0023] By the way, improving the dispersibility of the nonmagnetic powder in the nonmagnetic layer can lead to a reduction in the porosity of the nonmagnetic layer. In this regard, paragraph 0076 of JP 2020-144960 A (Patent Document 1) describes that in a nonmagnetic layer containing carbon black as a nonmagnetic powder, vinyl chloride resin is a binder that contributes to improving the dispersibility of carbon black. However, containing a large amount of vinyl chloride resin in the nonmagnetic layer increases the chlorine content (magnetic layer + nonmagnetic layer) of the magnetic recording medium. In addition, in the examples of JP 2004-103067 A (Patent Document 2) and the examples of JP 2005-267714 A (Patent Document 3), α-iron oxide powder accounts for most of the nonmagnetic powder in the nonmagnetic layer (see paragraph 0081 of JP 2004-103067 A (Patent Document 2) and paragraph 0085 of JP 2005-267714 A (Patent Document 3)). However, if the non-magnetic powder in the non-magnetic layer is mostly α-iron oxide powder, the iron content of the magnetic recording medium (magnetic layer + non-magnetic layer) will be high. In contrast, adding carbon black as described below to the non-magnetic layer and adding a binder as described below is preferable for reducing the porosity of the non-magnetic layer while keeping the chlorine content (magnetic layer + non-magnetic layer) and iron content (magnetic layer + non-magnetic layer) of the magnetic recording medium low.

[0024] (Non-magnetic powder) The non-magnetic layer is a layer containing at least a non-magnetic powder. The non-magnetic powder contained in the non-magnetic layer may be one type of non-magnetic powder or two or more types of non-magnetic powder. As the non-magnetic powder, it is preferable to use at least carbon black, and it is more preferable to use carbon black having a pH in the range of 7.0 to 10.0. In the present invention and this specification, the pH of the non-magnetic powder such as carbon black is a value measured according to the standard test method ASTM D1512.

[0025] Carbon black generally has a graphite structure, which is a condensed polycyclic aromatic structure, and the structure contains freely movable π electrons, which lead to good electrical conductivity. Therefore, carbon black can exhibit properties as an electron donor, and when dispersed in water, the H generated by the dissociation of water is converted into + ions and OH - H in ions + Selectively adsorbs ions and OH - This results in leaving ions behind, resulting in a basic pH. This is because carbon black is mainly composed of the original graphite structure and retains an abundance of π electrons. On the other hand, carbon black that exhibits an acidic pH is also commercially available. Carbon black that exhibits an acidic pH has oxygen introduced into its structure by oxidation treatment. The oxygen chemically bonds with carbon (C) to form acidic functional groups such as hydroxyl groups and carboxyl groups. This oxygen-carbon chemical bond reduces the electron donor properties, lowering the pH, and the pH of the carbon black becomes acidic. Therefore, it can be said that in carbon black that exhibits an acidic pH, the original graphite structure has been chemically altered and the condensed polycyclic aromatic structures have been reduced. For the above reasons, the present inventor believes that carbon black exhibiting a neutral to alkaline pH range of 7.0 to 10.0 has more condensed polycyclic aromatic structures than carbon black exhibiting an acidic pH. From the viewpoint of improving dispersibility, binders that are preferably used in combination with carbon black exhibiting a pH range of 7.0 to 10.0 will be described later.

[0026] Carbon black can be produced, for example, by the furnace process, in which petroleum-based or coal-based oil is blown into high-temperature gas and incompletely combusted to obtain carbon black. Carbon black produced by the furnace process is called furnace black. The following carbon blacks are also known as carbon blacks: Lamp black produced by the lamp black process, in which oil, pine, etc. are burned in a shallow dish; acetylene black produced by the acetylene black process, in which acetylene gas is pyrolyzed; thermal black produced by the thermal black process, in which other hydrocarbon gases are pyrolyzed; and channel black produced by the channel black process, in which natural gas, aromatic oils, etc. are partially oxidized. As carbon black exhibiting a pH in the range of 7.0 to 10.0, which is neutral to alkaline, for example, carbon black selected from the group consisting of furnace black, lamp black, acetylene black, and thermal black can be used. In contrast, channel black tends to exhibit an acidic pH. However, the method for producing the carbon black contained in the nonmagnetic layer is not particularly limited.

[0027] From the viewpoint of reducing the void ratio of the non-magnetic layer, the specific surface area of ​​the carbon black is 280 m 2 / g or more, and 2 From the viewpoint of easiness in improving the dispersibility of carbon black in the nonmagnetic layer, the specific surface area of ​​carbon black is preferably 500 m 2 / g or less, and 2 / g or less is more preferable. In the present invention and this specification, the specific surface area of ​​various powders is the specific surface area calculated using the BET (Brunauer-Emmett-Teller) formula derived by Brunauer, Emmett and Teller by the nitrogen adsorption method according to JIS K 6217-7:2013. The specific surface area of ​​various powders used in the examples and comparative examples described below is the specific surface area measured for the raw material powder used in the preparation of each layer-forming composition. However, the powder can also be extracted from the magnetic recording medium by a known method and the specific surface area of ​​the extracted powder can also be calculated. This also applies to the pH of the powder.

[0028] The proportion of carbon black in the nonmagnetic powder of the nonmagnetic layer is preferably 50.0% by mass or more, more preferably 60.0% by mass or more, 70.0% by mass or more, 80.0% by mass or more, 90.0% by mass or more, and even more preferably 100.0% by mass (i.e., the nonmagnetic powder is only carbon black) relative to the total amount of the nonmagnetic powder. The proportion of carbon black in the nonmagnetic powder of the nonmagnetic layer can be 100.0% by mass or less, less than 100.0% by mass, less than 99.0% by mass, or less than 95.0% by mass relative to the total amount of the nonmagnetic powder. The content (filling rate) of the nonmagnetic powder in the nonmagnetic layer is preferably in the range of 50 to 90% by mass, more preferably in the range of 60 to 90% by mass, relative to the total mass of the nonmagnetic layer.

[0029] As the non-magnetic powder other than carbon black, an inorganic powder or an organic powder may be used. The average particle size of the non-magnetic powder other than carbon black is preferably in the range of 10 to 200 nm, more preferably in the range of 10 to 100 nm. The specific surface area of ​​the non-magnetic powder other than carbon black is, for example, 60 to 150 m 2 The pH of the non-magnetic powder other than carbon black can be in the range of, for example, 7.0 to 10.0. For example, inorganic powders include powders of metals, metal oxides, metal carbonates, metal sulfates, metal nitrides, metal carbides, metal sulfides, and the like. These non-magnetic powders are commercially available, and can also be produced by known methods. For details, see, for example, paragraphs 0146-0150 of JP 2011-216149 A. An example of the non-magnetic powder is α-iron oxide powder (also commonly called "red oxide"). However, if the non-magnetic powder in the non-magnetic layer is mostly α-iron oxide powder, the iron content (magnetic layer + non-magnetic layer) of the magnetic recording medium will be high. Therefore, in a non-magnetic layer containing α-iron oxide powder, the proportion of α-iron oxide powder in the non-magnetic layer is preferably less than 50.0 mass% of the total amount of non-magnetic powder, more preferably 40.0 mass% or less, and more preferably 30.0 mass% or less, 20.0 mass% or less, 10.0 mass% or less, and 5.0 mass% or less, in that order, and even more preferably 0.0 mass% (i.e., no α-iron oxide powder).

[0030] (Binding Agent) The magnetic recording medium may be a coating type magnetic recording medium, and the non-magnetic layer may contain a binder. The binder is one or more kinds of resin. In the present invention and this specification, the resin may be a homopolymer or a copolymer. As the binder of the non-magnetic layer, for example, a resin selected from polyurethane resin, polyester resin, polyamide resin, vinyl chloride resin, acrylic resin copolymerized with styrene, acrylonitrile, methyl methacrylate, etc., cellulose resin such as nitrocellulose, epoxy resin, phenoxy resin, polyvinyl acetal, polyvinyl butyral, etc. may be used alone or in combination. The average molecular weight of the resin used as the binder of the non-magnetic layer may be, for example, 5,000 to 200,000 or 10,000 to 200,000 in weight average molecular weight. In the present invention and this specification, the weight average molecular weight and number average molecular weight are values ​​obtained by converting values ​​measured under the following measurement conditions by gel permeation chromatography (GPC) into polystyrene equivalents, unless otherwise specified. The content of the binder can be, for example, 1.0 to 30.0 parts by mass with respect to 100.0 parts by mass of the nonmagnetic powder. GPC equipment: HLC-8120 (Tosoh Corporation) Column: TSK gel Multipore HXL-M (Tosoh Corporation, 7.8 mm ID (inner diameter) × 30.0 cm) Eluent: tetrahydrofuran (THF)

[0031] From the viewpoint of improving dispersibility, examples of binders that are preferably used in combination with carbon black having a pH in the range of 7.0 to 10.0 include polyurethane resins having aromatic ring structures. The present inventors believe that polyurethane resins having aromatic ring structures have high affinity and adsorptivity for carbon black having a pH in the range of 7.0 to 10.0, and therefore can contribute to improving the dispersibility of carbon black having a pH in the above range.

[0032] Examples of polyurethane resins include polyurethane resins with various skeletons such as polyether urethane, polyester urethane, polycarbonate urethane, and polyether ester urethane. The polyurethane resin having an aromatic ring structure can be, for example, a polyurethane resin synthesized using an isocyanate having an aromatic ring structure as an isocyanate compound that is a raw material for polyurethane. The urethane group concentration of the polyurethane resin synthesized using an isocyanate having an aromatic ring structure is preferably 1.0 meq / g to 5.0 meq / g, and more preferably 1.5 meq / g to 4.5 meq / g. The above polyurethane resin having a urethane group concentration of 1.0 meq / g or more, and even 1.5 meq / g or more, has a sufficient aromatic ring skeleton derived from the isocyanate having an aromatic ring structure contained in the polyurethane chain, and has good affinity and adsorption to carbon black. In addition, the above polyurethane resin having a urethane group concentration of 5.0 meq / g or less, and even 4.5 meq / g or less, has high solubility in a solvent that is usually used for producing a coating type magnetic recording medium, which can also contribute to improving the dispersibility of carbon black. "Eq" is an equivalent unit that cannot be converted to SI units.

[0033] Examples of polyols and isocyanate compounds used as raw materials for polyurethane resins include long-chain diols, short-chain diols and diisocyanate compounds described in "Polyurethane Resin Handbook" (edited by Iwata Keiji, published by Nikkan Kogyo Shimbun, 1986). The polyurethane chain may be linear, or may have a side chain structure and / or a branched structure.

[0034] In order to provide a polyurethane resin with a side chain structure, a compound having a side chain structure and two or more functional groups reactive with isocyanate in one molecule can be used. Examples of compounds having a side chain structure and two or more functional groups that react with isocyanate in one molecule include 1,2-propylene glycol, 1,3-propylene glycol, 1,3-butylene glycol, 2,3-butylene glycol, 2,2-dimethyl-1,3-propanediol, 3-methyl-1,5-pentanediol, 2,2,4-trimethyl-1,3-pentanediol, 2-ethyl-1,3-hexanediol, 2,2-dimethyl-3-hydroxypropyl-2',2'-dimethyl-3-hydroxypropanate, 2-normal butyl-2-ethyl-1,3-propanediol, 3-ethyl-1,5-pentanediol, 3-propyl-1,5-pentanediol, 2,2-diethyl-1,3-propanediol, 2-butyl, 2-ethyl-1,3-propanediol, 3- Octyl-1,5-pentanediol, 3-phenyl-1,5-pentanediol, 2,5-dimethyl-3-sodium sulfo-2,5-hexanediol, 1,3-bis(hydroxymethyl)cyclohexane, 1,4-bis(hydroxymethyl)cyclohexane, 1,4-bis(hydroxyethyl)cyclohexane, 1,4-bis(hydroxypropyl)cyclohexane, 1,4-bis(hydroxymethoxy)cyclohexane, 1,4-bis(hydroxyethoxy)cyclohexane, 2,2-bis(4-hydroxymethoxycyclohexyl)propane, 2,2-bis(4-hydroxyethoxycyclohexyl)propane, bis(4-hydroxycyclohexyl)methane, 2,2-bis(4-hydroxycyclohexyl)propane, 3(4),8(9)-tricyclo[5.2.1.0 2,6]decanedimethanol, hydrogenated bisphenol A, ethylene oxide adduct of hydrogenated bisphenol A, propylene oxide adduct of hydrogenated bisphenol A, etc. Compounds having a side chain structure and two or more functional groups reacting with isocyanate in one molecule include 2,2-dimethyl-1,3-propanediol, 2,2-dimethyl-3-hydroxypropyl-2',2'-dimethyl-3-hydroxypropanate, 2-normal butyl-2-ethyl-1,3-propanediol, 2,2-diethyl-1,3-propanediol, 2-butyl-2-ethyl-1,3-propanediol, 3(4),8(9)-tricyclo[5.2.1.0 2,6 ]Decanedimethanol, hydrogenated bisphenol A having an alicyclic skeleton, an ethylene oxide adduct of hydrogenated bisphenol A, and a propylene oxide adduct of hydrogenated bisphenol A are preferred, and hydrogenated bisphenol A having an alicyclic skeleton is more preferred.

[0035] In order to give the polyurethane resin a branched structure, a small amount of trifunctional or higher alcohol can be used in addition to the diol compound during polyurethane polymerization. As the trifunctional or higher alcohol, trimethylolpropane, glycerin, pentaerythritol, or their ethylene oxide adducts, propylene oxide adducts, etc. are preferred.

[0036] For example, when the polyurethane resin is a polyester urethane, it preferably has the following skeleton.

[0037] When the total of the acid component and glycol component of the polyester polyol is taken as 100 mol %, it is preferable that the polyester polyol contains 20 mol % or more of aromatic dibasic acid, and the remainder is composed of aliphatic and / or alicyclic dibasic acid. Furthermore, it is preferable that the polyester polyol contains 50 to 100 mol % of aliphatic diol components having an alkyl group having 1 or more carbon atoms in the side chain of the total diol components. It is preferable that the polyester polyol contains 20 mol % or more of aromatic dibasic acid from the viewpoint of improving the dispersibility of carbon black and the running durability of magnetic recording media. In addition, the molar ratio of dibasic acid / glycol is not limited to 1 / 1, and it is also preferable that the glycol component is in excess. The preferable range is 1 / 1 to 1 / 2.5.

[0038] Examples of aromatic dibasic acids include terephthalic acid, isophthalic acid, orthophthalic acid, naphthalenedicarboxylic acid, etc. Among these, isophthalic acid and orthophthalic acid are preferred from the viewpoint of achieving both the dispersibility of carbon black and the running durability of the magnetic recording medium.

[0039] Examples of the aliphatic diol component having an alkyl group having one or more carbon atoms in the side chain include 1,2-propylene glycol, 1,3-butylene glycol, 2,3-butylene glycol, 2-methyl-1,3-propanediol, 2,2-dimethyl-1,3-propanediol, 3-methyl-1,5-pentanediol, 2,2-dimethyl-3-hydroxypropyl-2',2'-dimethyl-3-hydroxypropanate, 2-butyl, 2-ethyl-1,3-propanediol, 2,2-diethyl-1,3-propanediol, etc. Among these, 2,2-dimethyl-1,3-propanediol, 2,2-diethyl-1,3-propanediol, 2-butyl, 2-ethyl-1,3-propanediol, and 2,2-dimethyl-3-hydroxypropyl-2',2'-dimethyl-3-hydroxypropanate are preferred.

[0040] Other diol components used in the polyester polyol include aliphatic glycols such as ethylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, and 1,6-hexanediol, 1,3-bis(hydroxymethyl)cyclohexane, 1,4-bis(hydroxymethyl)cyclohexane, 1,4-bis(hydroxyethyl)cyclohexane, 1,4-bis(hydroxypropyl)cyclohexane, 1,4-bis(hydroxymethoxy)cyclohexane, 1,4-bis(hydroxyethoxy)cyclohexane, 2,2-bis(4-hydroxymethoxycyclohexyl)propane, 2,2-bis(4-hydroxyethoxycyclohexyl)propane, bis(4-hydroxycyclohexyl)methane, 2,2-bis(4-hydroxycyclohexyl)propane, 3(4),8(9)-tricyclo[5.2.1.0]cyclopentadiene, and the like. 2,6 ]decanedimethanol and other alicyclic glycols. Among these, 1,3-propanediol, 1,4-bis(hydroxymethyl)cyclohexane and 3(4),8(9)-tricyclo[5.2.1.0 2,6 ]Decanedimethanol is preferred.

[0041] The polyester polyol preferably has a number average molecular weight of 300 to 800, calculated from the hydroxyl value measured by the method described in JIS standard K1557-1:2007, from the viewpoint of obtaining a polyurethane resin that is highly soluble in solvents commonly used in the production of particulate magnetic recording media.

[0042] Examples of aromatic isocyanates used in the synthesis of polyurethane resin include 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, p-phenylene diisocyanate, 4,4'-diphenylmethane diisocyanate, m-phenylene diisocyanate, 3,3'-dimethoxy-4,4'-biphenylene diisocyanate, 2,6-naphthalene diisocyanate, 3,3'-dimethyl-4,4'-biphenylene diisocyanate, 4,4'-diphenylene diisocyanate, 4,4'-diisocyanate diphenyl ether, 1,5-naphthalene diisocyanate, m-xylene diisocyanate, etc. Among these, 4,4'-diphenylmethane diisocyanate is more preferred.

[0043] For the short-chain diol component used in the synthesis of the polyurethane resin, the above description of other diol components used in the polyester polyol and the above description of the compound having a side chain structure and two or more functional groups reactive with isocyanate in one molecule can be referred to. Specific examples of the short-chain diol include the short-chain diol used in the synthesis of the polyurethane resin A described below. The use of a short-chain diol having a side chain structure in the synthesis of the polyurethane resin is preferable from the viewpoint of increasing the solvent solubility of the unit in which the short-chain diol and aromatic isocyanate are bonded.

[0044] The polyurethane resin preferably contains a metal sulfonate salt group in the skeleton from the viewpoint of improving the dispersibility of carbon black having a pH in the range of 7.0 to 10.0. The metal sulfonate salt group has the function of adsorbing to the basic site on the surface of carbon black. The content of the metal sulfonate salt group in the polyurethane resin is preferably in the range of 60 to 400 eq / ton from the viewpoint of improving the dispersibility of carbon black having a pH in the above range and improving the solvent solubility of the polyurethane resin. As a method for introducing the metal sulfonate salt group into the polyurethane resin, for example, 5-Na sulfoisophthalic acid or 5-K sulfoisophthalic acid is copolymerized in a polyester polyol, or a diol containing a metal sulfonate salt group is used.

[0045] The number average molecular weight of the polyurethane resin is preferably in the range of 5,000 to 100,000, more preferably in the range of 10,000 to 80,000. The polyurethane resin may be synthesized by either a method in which the raw material is in a molten state or a method in which the raw material is dissolved in a solution. As the reaction catalyst, stannous octoate, dibutyltin dilaurate, triethylamine, etc. may be used. In addition, an ultraviolet absorber, a hydrolysis inhibitor, an oxidation inhibitor, etc. may be added before, during, or after the production of the polyurethane resin.

[0046] The content of the polyurethane resin having an aromatic ring structure is preferably 50.0 mass% or more relative to the total amount of binder in the non-magnetic layer, and more preferably 60.0 mass% or more, 70.0 mass% or more, 80.0 mass% or more, 90.0 mass% or more, and 95.0 mass% or more, in that order, and is even more preferably 100.0 mass% (i.e. the binder in the non-magnetic layer is only the polyurethane resin having an aromatic ring structure).

[0047] As the binder of the non-magnetic layer, only one or more kinds of polyurethane resins having aromatic ring structures may be used, or one or more kinds of polyurethane resins having aromatic ring structures and one or more kinds of resins other than polyurethane resins having aromatic ring structures may be used. Since vinyl chloride resin can increase the chlorine content (magnetic layer + non-magnetic layer) of the magnetic recording medium, when the binder of the non-magnetic layer contains vinyl chloride resin, it is preferably 50.0 mass% or less, more preferably 40.0 mass% or less, 30.0 mass% or less, 20.0 mass% or less, 10.0 mass% or less, 5.0 mass% or less, and more preferably 0.0 mass% (i.e., no vinyl chloride resin).

[0048] In the nonmagnetic layer, one or more other known additives can be used in any amount, appropriately selected from commercially available products according to the desired properties, or produced by known methods. For additives that can be contained in the nonmagnetic layer, see the description below.

[0049] In the present invention and this specification, the nonmagnetic layer also includes a substantially nonmagnetic layer that contains a small amount of ferromagnetic powder, for example as an impurity or intentionally, together with the nonmagnetic powder. Here, the substantially nonmagnetic layer refers to a layer whose residual magnetic flux density is 10 mT or less, whose coercive force is 100 Oe or less, or whose residual magnetic flux density is 10 mT or less and whose coercive force is 100 Oe or less. In terms of the unit Oe, 1 [kOe] = 106 / 4π [A / m]. It is preferable that the nonmagnetic layer has no residual magnetic flux density or coercive force.

[0050] <Magnetic layer> (Ferromagnetic powder) As the ferromagnetic powder contained in the magnetic layer, a known ferromagnetic powder can be used as the ferromagnetic powder used in the magnetic layer of various magnetic recording media. It is preferable to use a ferromagnetic powder with a small average particle size from the viewpoint of improving recording density. From this viewpoint, the average particle size of the ferromagnetic powder is preferably 50 nm or less, more preferably 45 nm or less, even more preferably 40 nm or less, even more preferably 35 nm or less, even more preferably 30 nm or less, even more preferably 25 nm or less, and even more preferably 20 nm or less. On the other hand, from the viewpoint of magnetization stability, the average particle size of the ferromagnetic powder is preferably 5 nm or more, more preferably 8 nm or more, even more preferably 10 nm or more, and even more preferably 15 nm or more.

[0051] Hexagonal Ferrite Powder A preferred specific example of the ferromagnetic powder is hexagonal ferrite powder. For details of the hexagonal ferrite powder, see, for example, JP2011-225417A, paragraphs 0012-0030, JP2011-216149A, paragraphs 0134-0136, JP2012-204726A, paragraphs 0013-0030, and JP2015-127985A, paragraphs 0029-0084.

[0052] In the present invention and this specification, the term "hexagonal ferrite powder" refers to a ferromagnetic powder in which the crystal structure of hexagonal ferrite is detected as the main phase by X-ray diffraction analysis. The main phase refers to the structure to which the diffraction peak with the highest intensity is assigned in the X-ray diffraction spectrum obtained by X-ray diffraction analysis. For example, when the diffraction peak with the highest intensity in the X-ray diffraction spectrum obtained by X-ray diffraction analysis is assigned to the crystal structure of hexagonal ferrite, it is determined that the crystal structure of hexagonal ferrite is detected as the main phase. When only a single structure is detected by X-ray diffraction analysis, the detected structure is regarded as the main phase. The crystal structure of hexagonal ferrite contains at least an iron atom, a divalent metal atom, and an oxygen atom as constituent atoms. The divalent metal atom is a metal atom that can become a divalent cation as an ion, and examples of the divalent metal atom include an alkaline earth metal atom such as a strontium atom, a barium atom, and a calcium atom, and a lead atom. In the present invention and this specification, the hexagonal strontium ferrite powder refers to a powder in which the main divalent metal atom contained therein is a strontium atom, and the hexagonal barium ferrite powder refers to a powder in which the main divalent metal atom contained therein is a barium atom. The main divalent metal atom refers to the divalent metal atom that is the most abundant of the divalent metal atoms contained in the powder on an atomic % basis. However, the above divalent metal atoms do not include rare earth atoms. In the present invention and this specification, the "rare earth atom" is selected from the group consisting of scandium atoms (Sc), yttrium atoms (Y), and lanthanoid atoms. The lanthanide atom is selected from the group consisting of a lanthanum atom (La), a cerium atom (Ce), a praseodymium atom (Pr), a neodymium atom (Nd), a promethium atom (Pm), a samarium atom (Sm), a europium atom (Eu), a gadolinium atom (Gd), a terbium atom (Tb), a dysprosium atom (Dy), a holmium atom (Ho), an erbium atom (Er), a thulium atom (Tm), a ytterbium atom (Yb), and a lutetium atom (Lu).

[0053] Hereinafter, hexagonal strontium ferrite powder, which is one form of hexagonal ferrite powder, will be described in more detail.

[0054] The activation volume of the hexagonal strontium ferrite powder is preferably 800 to 1500 nm 3 The finely divided hexagonal strontium ferrite powder exhibiting an activation volume in the above range is suitable for producing a magnetic recording medium exhibiting excellent electromagnetic conversion characteristics. The activation volume of the hexagonal strontium ferrite powder is preferably 800 nm 3 For example, 850 nm or more. 3 From the viewpoint of further improving the electromagnetic conversion characteristics, the activation volume of the hexagonal strontium ferrite powder can be 1400 nm or more. 3 More preferably, it is 1300 nm or less. 3 More preferably, it is 1200 nm or less. 3 More preferably, it is equal to or less than 1100 nm. 3 It is even more preferable that the activation volume is not more than 100%. It is also preferable that the activation volume of the hexagonal barium ferrite powder is in the above range.

[0055] "Activation volume" is a unit of magnetization reversal and is an index showing the magnetic size of a particle. The activation volume described in this invention and this specification and the anisotropy constant Ku described below are values ​​obtained by measuring the coercive force Hc measurement section at magnetic field sweep speeds of 3 minutes and 30 minutes (measurement temperature: 23°C ± 1°C) using a vibrating sample magnetometer and calculating from the following relationship between Hc and activation volume V. The unit of the anisotropy constant Ku is 1 erg / cc = 1.0 x 10 -1 J / m 3 It is. Hc=2Ku / Ms{1-[(kT / KuV)ln(At / 0.693)] 1 / 2} [In the above formula, Ku: anisotropy constant (unit: J / m 3 ), Ms: saturation magnetization (unit: kA / m), k: Boltzmann constant, T: absolute temperature (unit: K), V: activation volume (unit: cm 3 ), A: spin precession frequency (unit: s -1 ), t: magnetic field reversal time (unit: s)]

[0056] The anisotropy constant Ku can be used as an index of reduction in thermal fluctuation, in other words, improvement in thermal stability. The hexagonal strontium ferrite powder is preferably 1.8×10 5 J / m 3 More preferably, the Ku is 2.0×10 or more. 5 J / m 3 The Ku of the hexagonal strontium ferrite powder can be, for example, 2.5×10 5 J / m 3 However, since a higher Ku value means higher thermal stability and is preferable, the Ku value is not limited to the above-mentioned values.

[0057] The hexagonal strontium ferrite powder may or may not contain rare earth atoms. When the hexagonal strontium ferrite powder contains rare earth atoms, it is preferable that the rare earth atoms are contained at a content (bulk content) of 0.5 to 5.0 atomic % relative to 100 atomic % of iron atoms. In one embodiment, the hexagonal strontium ferrite powder containing rare earth atoms can have uneven distribution of rare earth atoms in the surface layer portion. In the present invention and this specification, the term "surface distribution of rare earth atoms" refers to the rare earth atom content relative to 100 atomic % of iron atoms in a solution obtained by partially dissolving a hexagonal strontium ferrite powder in an acid (hereinafter referred to as "surface content of rare earth atoms" or simply "surface content" for rare earth atoms), which is greater than the rare earth atom content relative to 100 atomic % of iron atoms in a solution obtained by completely dissolving a hexagonal strontium ferrite powder in an acid (hereinafter referred to as "bulk content of rare earth atoms" or simply "bulk content" for rare earth atoms), Rare earth atom surface content / rare earth atom bulk content>1.0 The rare earth atom content of the hexagonal strontium ferrite powder described later is synonymous with the rare earth atom bulk content. In contrast, partial dissolution using an acid dissolves the surface layer of the particles constituting the hexagonal strontium ferrite powder, so the rare earth atom content in the solution obtained by partial dissolution is the rare earth atom content in the surface layer of the particles constituting the hexagonal strontium ferrite powder. The rare earth atom surface layer content satisfying the ratio of "rare earth atom surface layer content / rare earth atom bulk content>1.0" means that the rare earth atoms are unevenly distributed (i.e., more present in the surface layer) in the particles constituting the hexagonal strontium ferrite powder. In the present invention and this specification, the surface layer refers to a portion of the region extending from the surface of the particles constituting the hexagonal strontium ferrite powder toward the inside.

[0058] When the hexagonal strontium ferrite powder contains rare earth atoms, the rare earth atom content (bulk content) is preferably in the range of 0.5 to 5.0 atomic % relative to 100 atomic % of iron atoms. It is considered that the rare earth atoms contained in the bulk content in the above range and the rare earth atoms unevenly distributed in the surface layer of the particles constituting the hexagonal strontium ferrite powder contribute to suppressing the decrease in the reproduction output during repeated reproduction. This is presumed to be because the hexagonal strontium ferrite powder contains rare earth atoms in the bulk content in the above range and the rare earth atoms unevenly distributed in the surface layer of the particles constituting the hexagonal strontium ferrite powder can increase the anisotropy constant Ku. The higher the value of the anisotropy constant Ku, the more the occurrence of a phenomenon called thermal fluctuation can be suppressed (in other words, the thermal stability can be improved). By suppressing the occurrence of thermal fluctuation, the decrease in the reproduction output during repeated reproduction can be suppressed. It is speculated that the uneven distribution of rare earth atoms in the surface layer of hexagonal strontium ferrite powder particles contributes to stabilizing the spin of the iron (Fe) sites in the crystal lattice of the surface layer, thereby increasing the anisotropy constant Ku. In addition, it is presumed that using the hexagonal strontium ferrite powder having rare earth atom uneven distribution on the surface as the ferromagnetic powder of the magnetic layer also contributes to suppressing the wear of the magnetic layer surface due to sliding with the magnetic head. That is, it is presumed that the hexagonal strontium ferrite powder having rare earth atom uneven distribution on the surface can also contribute to improving the running durability of the magnetic recording medium. This is presumed to be because the uneven distribution of rare earth atoms on the surface of the particles constituting the hexagonal strontium ferrite powder contributes to improving the interaction between the particle surface and the organic substance (e.g., binder and / or additive) contained in the magnetic layer, and as a result, the strength of the magnetic layer is improved. From the viewpoint of further suppressing the decrease in regeneration output during repeated regeneration and / or further improving running durability, the rare earth atom content (bulk content) is more preferably in the range of 0.5 to 4.5 atomic %, even more preferably in the range of 1.0 to 4.5 atomic %, and even more preferably in the range of 1.5 to 4.5 atomic %.

[0059] The bulk content is the content obtained by completely dissolving the hexagonal strontium ferrite powder. In the present invention and this specification, unless otherwise specified, the content of an atom refers to the bulk content obtained by completely dissolving the hexagonal strontium ferrite powder. The hexagonal strontium ferrite powder containing rare earth atoms may contain only one rare earth atom as a rare earth atom, or may contain two or more rare earth atoms. The bulk content when containing two or more rare earth atoms is obtained for the total of two or more rare earth atoms. This point is the same for other components in the present invention and this specification. That is, unless otherwise specified, a certain component may be used only one type, or two or more types may be used. When two or more types are used, the content or content refers to the total of two or more types.

[0060] When the hexagonal strontium ferrite powder contains rare earth atoms, the rare earth atoms contained therein may be any one or more of rare earth atoms. From the viewpoint of further suppressing the decrease in the reproduction output during repeated reproduction, preferred rare earth atoms include neodymium atoms, samarium atoms, yttrium atoms and dysprosium atoms, more preferred are neodymium atoms, samarium atoms and yttrium atoms, and even more preferred are neodymium atoms.

[0061] In the hexagonal strontium ferrite powder having rare earth atom uneven distribution in the surface layer, the rare earth atoms may be unevenly distributed in the surface layer of the particles constituting the hexagonal strontium ferrite powder, and the degree of uneven distribution is not limited. For example, for the hexagonal strontium ferrite powder having rare earth atom uneven distribution in the surface layer, the ratio of the surface content of rare earth atoms obtained by partial dissolution under the dissolution conditions described below to the bulk content of rare earth atoms obtained by complete dissolution under the dissolution conditions described below, "surface content / bulk content", is more than 1.0 and can be 1.5 or more. The "surface content / bulk content" being greater than 1.0 means that the rare earth atoms are unevenly distributed in the surface layer (i.e., more than in the interior) in the particles constituting the hexagonal strontium ferrite powder. In addition, the ratio of the surface layer content of rare earth atoms obtained by partial dissolution under the dissolution conditions described later to the bulk content of rare earth atoms obtained by total dissolution under the dissolution conditions described later, "surface layer content / bulk content", can be, for example, 10.0 or less, 9.0 or less, 8.0 or less, 7.0 or less, 6.0 or less, 5.0 or less, or 4.0 or less. However, in a hexagonal strontium ferrite powder having rare earth atom surface layer uneven distribution, it is sufficient that the rare earth atoms are unevenly distributed in the surface layer of the particles constituting the hexagonal strontium ferrite powder, and the above "surface layer content / bulk content" is not limited to the upper or lower limit exemplified.

[0062] The partial and total dissolution of hexagonal strontium ferrite powder will be described below. For hexagonal strontium ferrite powder present as powder, the sample powders to be partially and completely dissolved are taken from the same lot of powder. On the other hand, for hexagonal strontium ferrite powder contained in the magnetic layer of a magnetic recording medium, a part of the hexagonal strontium ferrite powder taken out of the magnetic layer is subjected to partial dissolution, and the other part is subjected to total dissolution. The hexagonal strontium ferrite powder can be taken out of the magnetic layer by, for example, the method described in paragraph 0032 of JP 2015-91747 A. The above-mentioned partial dissolution means that the hexagonal strontium ferrite powder is dissolved to such an extent that the remaining powder can be visually confirmed in the liquid at the end of dissolution. For example, the partial dissolution can dissolve a region of 10 to 20 mass% of the particles constituting the hexagonal strontium ferrite powder, with the whole particles being 100 mass%. On the other hand, the above-mentioned complete dissolution means that the hexagonal strontium ferrite powder is dissolved to such an extent that the remaining powder cannot be visually confirmed in the liquid at the end of dissolution. The partial dissolution and the surface layer content are measured, for example, by the following method. Note that the dissolution conditions such as the amount of sample powder are merely examples, and any dissolution conditions that allow partial or complete dissolution can be used. A container (e.g., a beaker) containing 12 mg of sample powder and 10 ml of 1 mol / L hydrochloric acid is placed on a hot plate set at 70°C for 1 hour. The resulting solution is filtered through a 0.1 μm membrane filter. Elemental analysis of the filtrate thus obtained is performed using an inductively coupled plasma (ICP) analyzer. In this way, the surface layer content of rare earth atoms relative to 100 atomic % of iron atoms can be determined. When multiple types of rare earth atoms are detected by elemental analysis, the total content of all rare earth atoms is taken as the surface layer content. This is also true for the measurement of bulk content. On the other hand, the total dissolved and bulk contents are measured, for example, by the following method. A container (e.g., a beaker) containing 12 mg of sample powder and 10 ml of 4 mol / L hydrochloric acid is placed on a hot plate set at 80° C. for 3 hours. After that, the same procedure is carried out as for the partial dissolution and surface layer content measurement described above, and the bulk content relative to 100 atomic % of iron atoms can be obtained.

[0063] From the viewpoint of increasing the reproduction output when reproducing data recorded on a magnetic recording medium, it is desirable for the mass magnetization σs of the ferromagnetic powder contained in the magnetic recording medium to be high. In this regard, hexagonal strontium ferrite powder containing rare earth atoms but not having uneven distribution of rare earth atoms in the surface layer has a tendency to have a significantly lower σs than hexagonal strontium ferrite powder not containing rare earth atoms. In contrast, hexagonal strontium ferrite powder having uneven distribution of rare earth atoms in the surface layer is considered to be preferable in terms of suppressing such a large decrease in σs. In one embodiment, the σs of the hexagonal strontium ferrite powder is 45 A·m 2 / kg or more, and 47A·m 2 / kg or more. On the other hand, from the viewpoint of noise reduction, σs is 80A·m 2 / kg or less, and 60A·m 2 / kg or less is more preferable. σs can be measured using a known measuring device capable of measuring magnetic properties, such as a vibrating sample magnetometer. In the present invention and this specification, unless otherwise specified, the mass magnetization σs is a value measured at a magnetic field strength of 15 kOe.

[0064] Regarding the content (bulk content) of the constituent atoms of the hexagonal strontium ferrite powder, the strontium atom content can be, for example, in the range of 2.0 to 15.0 atomic % relative to 100 atomic % of iron atoms. In one embodiment, the divalent metal atoms contained in the hexagonal strontium ferrite powder can be only strontium atoms. In another embodiment, the hexagonal strontium ferrite powder can also contain one or more other divalent metal atoms in addition to strontium atoms. For example, it can contain barium atoms and / or calcium atoms. When divalent metal atoms other than strontium atoms are contained, the barium atom content and calcium atom content in the hexagonal strontium ferrite powder can each be, for example, in the range of 0.05 to 5.0 atomic % relative to 100 atomic % of iron atoms.

[0065] Known crystal structures of hexagonal ferrite include magnetoplumbite type (also called "M type"), W type, Y type, and Z type. The hexagonal strontium ferrite powder may have any of the crystal structures. The crystal structure can be confirmed by X-ray diffraction analysis. The hexagonal strontium ferrite powder may be one in which a single crystal structure or two or more types of crystal structures are detected by X-ray diffraction analysis. For example, in one embodiment, the hexagonal strontium ferrite powder may be one in which only the M-type crystal structure is detected by X-ray diffraction analysis. For example, M-type hexagonal ferrite is AFe 12 O 19Here, A represents a divalent metal atom, and when the hexagonal strontium ferrite powder is of the M type, A is only a strontium atom (Sr), or when A contains a plurality of divalent metal atoms, the strontium atom (Sr) accounts for the largest proportion on an atomic % basis as described above. The divalent metal atom content of the hexagonal strontium ferrite powder is usually determined by the type of crystal structure of the hexagonal ferrite, and is not particularly limited. The same applies to the iron atom content and the oxygen atom content. The hexagonal strontium ferrite powder contains at least an iron atom, a strontium atom, and an oxygen atom, and may further contain a rare earth atom. Furthermore, the hexagonal strontium ferrite powder may or may not contain atoms other than these atoms. As an example, the hexagonal strontium ferrite powder may contain an aluminum atom (Al). The content of aluminum atoms can be, for example, 0.5 to 10.0 atomic % relative to 100 atomic % of iron atoms. From the viewpoint of further suppressing the decrease in the reproduction output during repeated reproduction, the hexagonal strontium ferrite powder contains iron atoms, strontium atoms, oxygen atoms, and rare earth atoms, and the content of atoms other than these atoms is preferably 10.0 atomic % or less, more preferably in the range of 0 to 5.0 atomic %, relative to 100 atomic % of iron atoms, and may be 0 atomic %. That is, in one embodiment, the hexagonal strontium ferrite powder may not contain atoms other than iron atoms, strontium atoms, oxygen atoms, and rare earth atoms. The content expressed in atomic % above is obtained by converting the content (unit: mass %) of each atom obtained by completely dissolving the hexagonal strontium ferrite powder into a value expressed in atomic % using the atomic weight of each atom. In addition, in the present invention and this specification, "not containing" a certain atom means that the content measured by an ICP analyzer after completely dissolving is 0 mass %. The detection limit of an ICP analyzer is usually 0.01 ppm (parts per million) or less on a mass basis. The above term "free" is used to mean that the content is below the detection limit of the ICP analyzer.In one form, the hexagonal strontium ferrite powder can be one that does not contain bismuth atoms (Bi).

[0066] metal powder A specific preferred example of the ferromagnetic powder is a ferromagnetic metal powder. For details of the ferromagnetic metal powder, reference can be made to, for example, paragraphs 0137 to 0141 of JP 2011-216149 A and paragraphs 0009 to 0023 of JP 2005-251351 A.

[0067] ε-iron oxide powder A preferred specific example of the ferromagnetic powder is ε-iron oxide powder. In the present invention and this specification, the term "ε-iron oxide powder" refers to a ferromagnetic powder in which the ε-iron oxide crystal structure is detected as the main phase by X-ray diffraction analysis. For example, when the highest intensity diffraction peak in the X-ray diffraction spectrum obtained by X-ray diffraction analysis is assigned to the ε-iron oxide crystal structure, it is determined that the ε-iron oxide crystal structure is detected as the main phase. Known methods for producing ε-iron oxide powder include a method of producing it from goethite and a reverse micelle method. All of the above production methods are publicly known. In addition, for a method for producing ε-iron oxide powder in which a part of Fe is replaced by a substitution atom such as Ga, Co, Ti, Al, or Rh, reference can be made to, for example, J. Jpn. Soc. Powder Metallurgy Vol. 61 Supplement, No. S1, pp. S280-S284, J. Mater. Chem. C, 2013, 1, pp.5200-5206, etc. However, the method for producing the ε-iron oxide powder that can be used as the ferromagnetic powder in the magnetic layer of the magnetic recording medium is not limited to the method given here.

[0068] The activation volume of the ε-iron oxide powder is preferably 300 to 1500 nm 3 The finely divided ε-iron oxide powder exhibiting an activation volume in the above range is suitable for producing a magnetic recording medium exhibiting excellent electromagnetic conversion characteristics. The activation volume of the ε-iron oxide powder is preferably 300 nm 3For example, 500 nm or more. 3 From the viewpoint of further improving the electromagnetic conversion characteristics, the activation volume of the ε-iron oxide powder can be 1400 nm or more. 3 More preferably, it is 1300 nm or less. 3 More preferably, it is 1200 nm or less. 3 More preferably, it is equal to or less than 1100 nm. 3 It is even more preferred that:

[0069] The anisotropy constant Ku can be used as an index of the reduction in thermal fluctuation, in other words, the improvement in thermal stability. The ε-iron oxide powder is preferably 3.0×10 4 J / m 3 More preferably, the Ku is 8.0×10 or more. 4 J / m 3 The Ku of the ε-iron oxide powder can be, for example, 3.0×10 5 J / m 3 However, since a higher Ku value means higher thermal stability and is preferable, the Ku value is not limited to the above-mentioned values.

[0070] From the viewpoint of increasing the reproduction output when reproducing data recorded on the magnetic recording medium, it is desirable that the mass magnetization σs of the ferromagnetic powder contained in the magnetic recording medium is high. In this regard, in one embodiment, the σs of the ε-iron oxide powder is 8 A m 2 / kg or more, and 12 A m 2 On the other hand, the σs of ε-iron oxide powder is 40 A m 2 / kg or less, and 35A·m 2 It is more preferable that the amount is not more than 1 / kg.

[0071] In the present invention and this specification, unless otherwise specified, the average particle size of various powders such as ferromagnetic powders is a value measured by the following method using a transmission electron microscope. The powder is photographed at a magnification of 100,000 times using a transmission electron microscope, and a photograph of the particles that make up the powder is obtained by printing it on photographic paper or displaying it on a display so that the total magnification is 500,000 times. From the obtained particle photograph, the target particle is selected, and the particle outline is traced with a digitizer to measure the particle (primary particle) size. Primary particles are independent particles that are not aggregated. The above measurements are carried out for 500 randomly selected particles. The arithmetic mean of the particle sizes of the 500 particles thus obtained is the average particle size of the powder. As the transmission electron microscope, for example, a Hitachi transmission electron microscope H-9000 type can be used. The particle size can be measured using known image analysis software, for example, Carl Zeiss image analysis software KS-400. The average particle size shown in the Examples section below is a value measured using a Hitachi transmission electron microscope H-9000 type as the transmission electron microscope and Carl Zeiss image analysis software KS-400 as the image analysis software, unless otherwise specified. In the present invention and this specification, powder means a collection of multiple particles. For example, ferromagnetic powder means a collection of multiple ferromagnetic particles. In addition, the collection of multiple particles is not limited to a form in which the particles constituting the collection are in direct contact with each other, and also includes a form in which a binder, additive, etc., described later, are interposed between the particles. The term particle is sometimes used to refer to powder.

[0072] As a method for collecting a sample powder from a magnetic recording medium for particle size measurement, for example, the method described in paragraph 0015 of JP 2011-048878 A can be used.

[0073] In the present invention and this specification, unless otherwise specified, the size of the particles constituting the powder (particle size) is determined by the shape of the particles observed in the particle photograph. (1) In the case of needle-shaped, spindle-shaped, columnar (where the height is greater than the maximum major axis of the base), etc., it is expressed by the length of the major axis that constitutes the particle, i.e., the major axis length. (2) In the case of a plate or columnar shape (where the thickness or height is smaller than the maximum long diameter of the plate or base), it shall be expressed by the maximum long diameter of the plate or base. (3) In the case of a particle having a spherical, polyhedral, or unspecified shape, and the major axis of the particle cannot be specified from its shape, the particle is expressed as the equivalent circle diameter, which is determined by the circle projection method.

[0074] The average acicular ratio of a powder refers to the arithmetic average of the short axis length of the particles, i.e., the short axis length, the (long axis length / short axis length) value of each particle, and the values ​​obtained for the 500 particles. Here, unless otherwise specified, the short axis length refers to the length of the short axis constituting the particle in the above definition of particle size (1), and to the thickness or height in the above definition of particle size (2), and in the above definition of particle size (3), since there is no distinction between the long axis and the short axis, (long axis length / short axis length) is considered to be 1 for the sake of convenience. Unless otherwise specified, when the particle shape is specific, for example, in the case of the above definition of particle size (1), the average particle size is the average major axis length, in the case of definition (2), the average particle size is the average plate diameter, and in the case of definition (3), the average particle size is the average diameter (also called the average particle diameter or average particle size).

[0075] The content (filling rate) of the ferromagnetic powder in the magnetic layer is preferably in the range of 50 to 90 mass %, more preferably 60 to 90 mass %, relative to the total mass of the magnetic layer. A high filling rate of the ferromagnetic powder in the magnetic layer is preferable from the viewpoint of improving recording density.

[0076] (Non-magnetic powder) The magnetic recording medium may contain one or more types of non-magnetic powder in the magnetic layer. The non-magnetic powder preferably contains at least a non-magnetic powder that contributes to forming protrusions on the magnetic layer surface (hereinafter referred to as a "protrusion-forming agent"). The magnetic layer also preferably contains, as the non-magnetic powder, a non-magnetic powder that can function as an abrasive (hereinafter referred to as an "abrasive"). The protrusion-forming agent and the abrasive will be further described below.

[0077] Protrusion forming agent The protrusion-forming agent may be an inorganic powder or an organic powder. For example, examples of inorganic powders include inorganic oxides such as metal oxides, metal carbonates, metal sulfates, metal nitrides, metal carbides, and metal sulfides, and inorganic oxide powders are preferred. The average particle size of the protrusion-forming agent is preferably in the range of 90 to 200 nm, and more preferably in the range of 100 to 150 nm. In one embodiment, from the viewpoint of uniforming the friction characteristics, the particle size distribution of the protrusion-forming agent is preferably monodisperse, showing a single peak, rather than polydisperse, which has multiple peaks in the particle size distribution. From the viewpoint of easy availability of monodisperse particles, the protrusion-forming agent is preferably an inorganic powder, and more preferably a colloidal particle. In the present invention and this specification, the term "colloidal particles" refers to particles that can be dispersed without settling and provide a colloidal dispersion when added at 1 g per 100 mL of organic solvent to at least one organic solvent of methyl ethyl ketone, cyclohexanone, toluene, or ethyl acetate, or a mixed solvent containing two or more of the above solvents in any mixing ratio. If the non-magnetic powder used to form the magnetic layer is available, the non-magnetic powder contained in the magnetic layer can be determined to be colloidal particles by evaluating whether or not the non-magnetic powder has properties that meet the above definition of colloidal particles. Alternatively, it is also possible to evaluate whether or not the non-magnetic powder removed from the magnetic layer has properties that meet the above definition of colloidal particles.

[0078] Specific examples of colloidal particles include inorganic oxide colloidal particles such as SiO2, Al2O3, TiO2, ZrO2, and Fe2O3, and also include colloidal particles of composite inorganic oxides such as SiO2·Al2O3, SiO2·B2O3, TiO2·CeO2, SnO2·Sb2O3, SiO2·Al2O3·TiO2, and TiO2·CeO2·SiO2. Regarding the notation of composite inorganic oxides, "·" is used to indicate that it is a composite inorganic oxide of the inorganic oxides described before and after it. For example, SiO2·Al2O3 means a composite inorganic oxide of SiO2 and Al2O3. As colloidal particles, colloidal particles of silicon dioxide (silica), that is, silica colloidal particles (also called "colloidal silica"). In addition, for colloidal particles, the description in paragraphs 0048 to 0049 of JP 2017-68884 A can also be referred to.

[0079] The content of the protrusion-forming agent in the magnetic layer is preferably 0.1 to 10.0 parts by mass, more preferably 0.1 to 5.0 parts by mass, and even more preferably 1.0 to 5.0 parts by mass, relative to 100.0 parts by mass of the ferromagnetic powder. In the present invention and this specification, a certain component may be used alone or in combination of two or more types. When two or more types are used, the content refers to the total content of the two or more types.

[0080] (Abrasive) The abrasive is a component capable of removing the deposits that adhere to the magnetic head during running (abrasiveness). Examples of the abrasive include powders of alumina (Al2O3), silicon carbide, boron carbide (B4C), TiC, chromium oxide (Cr2O3), cerium oxide, zirconium oxide (ZrO2), iron oxide, diamond, etc., which are substances usually used as abrasives for magnetic layers, and among these, powders of alumina such as α-alumina, silicon carbide, and diamond are preferred. The content of the abrasive in the magnetic layer is preferably 1.0 to 20.0 parts by mass, more preferably 3.0 to 15.0 parts by mass, and even more preferably 4.0 to 10.0 parts by mass, per 100.0 parts by mass of ferromagnetic powder. In addition, with regard to the particle size of the abrasive, the specific surface area, which is an index of particle size, is, for example, 14 m 2 / g or more, preferably 16m 2 / g or more, more preferably 18m 2 The specific surface area of ​​the abrasive can be, for example, 40 m 2 / g or less.

[0081] (Binding agent, hardener) The magnetic recording medium may contain a binder in the magnetic layer. As the binder of the magnetic layer, various resins that are usually used as binders of coating-type magnetic recording media may be used. For example, as the binder of the magnetic layer, a resin selected from polyurethane resin, polyester resin, polyamide resin, vinyl chloride resin, acrylic resin copolymerized with styrene, acrylonitrile, methyl methacrylate, etc., cellulose resin such as nitrocellulose, epoxy resin, phenoxy resin, polyvinyl acetal, polyvinyl butyral, etc. may be used alone or in combination. Among these, preferred are polyurethane resin, acrylic resin, cellulose resin, and vinyl chloride resin. For the above binders, refer to paragraphs 0028 to 0031 of JP-A-2010-24113. The average molecular weight of the resin used as the binder of the magnetic layer may be, for example, 10,000 or more and 200,000 or less in weight average molecular weight. The content of the binder in the magnetic layer can be, for example, 1.0 to 30.0 parts by mass with respect to 100.0 parts by mass of the ferromagnetic powder.

[0082] A curing agent can also be used together with the resin usable as a binder. In one embodiment, the curing agent can be a thermosetting compound that undergoes a curing reaction (crosslinking reaction) by heating, and in another embodiment, it can be a photocuring compound that undergoes a curing reaction (crosslinking reaction) by irradiation with light. The curing agent can be included in the magnetic layer in a state where at least a part of the curing agent reacts (crosslinks) with other components such as the binder as the curing reaction proceeds during the magnetic layer formation process. This point is also true for layers formed using a composition that contains a curing agent when the composition used to form another layer contains a curing agent. A preferred curing agent is a thermosetting compound, and polyisocyanate is suitable. For details on polyisocyanate, refer to paragraphs 0124 to 0125 of JP 2011-216149 A. The curing agent can be used in an amount of, for example, 0 to 80.0 parts by mass relative to 100.0 parts by mass of the binder, and preferably 50.0 to 80.0 parts by mass from the viewpoint of improving the strength of the magnetic layer.

[0083] (Additives) The magnetic layer may further contain one or more additives as necessary. Examples of additives include the above-mentioned curing agents. Examples of additives contained in the magnetic layer include lubricants, dispersants, dispersion aids, antifungal agents, antistatic agents, antioxidants, and the like. Additives can be appropriately selected from commercially available products according to the desired properties, or can be produced by known methods and used in any amount. For example, for lubricants, refer to paragraphs 0030 to 0033, 0035, and 0036 of JP-A-2016-126817. The non-magnetic layer described below may contain a lubricant. For lubricants that may be contained in the non-magnetic layer, refer to paragraphs 0030 to 0031, 0034, 0035, and 0036 of JP-A-2016-126817. For dispersants, refer to paragraphs 0061 and 0071 of JP-A-2012-133837. A dispersant may be added to the nonmagnetic layer forming composition. For dispersants that can be added to the nonmagnetic layer forming composition, refer to paragraph 0061 of JP2012-133837A. As an example of an additive that can be used to improve the dispersibility of an abrasive in a magnetic layer containing an abrasive, the dispersants described in paragraphs 0012 to 0022 of JP2013-131285A can be mentioned.

[0084] <Nonmagnetic support> Next, the non-magnetic support (hereinafter, simply referred to as "support") will be described. Examples of the non-magnetic support include known biaxially stretched polyethylene terephthalate, polyethylene naphthalate, polyamide, polyamideimide, aromatic polyamide, and the like. Among these, polyethylene terephthalate, polyethylene naphthalate, and polyamide are preferred. These supports may be previously subjected to corona discharge, plasma treatment, easy-adhesion treatment, heat treatment, and the like.

[0085] <Backcoat layer> The magnetic recording medium may have a backcoat layer containing a nonmagnetic powder on the surface side opposite to the surface side having the magnetic layer and the nonmagnetic layer of the nonmagnetic support. Alternatively, the magnetic recording medium may be a magnetic recording medium without a backcoat layer. The backcoat layer preferably contains either or both of carbon black and inorganic powder. For details of the backcoat layer, known techniques related to the backcoat layer may be applied. The backcoat layer may also contain a binder. For the binder contained in the backcoat layer and various additives that may be optionally contained, the above description and known techniques related to the formulation of the magnetic layer and / or nonmagnetic layer may be applied arbitrarily. For example, the description in paragraphs 0018-0020 of JP-A-2006-331625 and the description in column 4, line 65 to column 5, line 38 of US Pat. No. 7,029,774 may be referred to for the backcoat layer.

[0086] <Manufacturing process> (Preparation of compositions for forming each layer) The composition for forming the magnetic layer, non-magnetic layer or backcoat layer usually contains a solvent in addition to the various components described above. As the solvent, one or more of the various solvents usually used in the manufacture of coating-type magnetic recording media can be used. The solvent content of each layer-forming composition is not particularly limited. For the solvent, refer to paragraph 0153 of JP 2011-216149 A. The solid content concentration and solvent composition of each layer-forming composition may be appropriately adjusted according to the handling suitability of the composition, the coating conditions and the thickness of each layer to be formed. The process for preparing the composition for forming the magnetic layer, non-magnetic layer or backcoat layer usually includes at least a kneading process, a dispersion process, and a mixing process provided before or after these processes as necessary. Each individual process may be divided into two or more stages. The centrifugation process of the dispersion of the protrusion-forming agent is as described above. All the raw materials used in the preparation of each layer-forming composition may be added at the beginning or during any process. In addition, each raw material may be added in two or more steps in separate steps. For example, the binder may be added in portions in the kneading step, the dispersing step, and the mixing step for adjusting the viscosity after dispersion. In the manufacturing process of the magnetic recording medium, conventional known manufacturing techniques may be used as some of the steps. In the kneading step, it is preferable to use an open kneader, a continuous kneader, a pressure kneader, an extruder, or the like that has a strong kneading force. Details of the kneading step are described in JP-A-1-106338 and JP-A-1-79274. As the dispersing machine, various known dispersing machines that utilize shear force, such as a bead mill, a ball mill, a sand mill, or a homomixer, may be used. Dispersing beads may be preferably used for dispersion. Examples of dispersing beads include ceramic beads and glass beads, and zirconia beads are preferred. Two or more types of beads may be used in combination. The bead diameter (particle size) and bead packing rate of the dispersing beads are not particularly limited and may be set according to the powder to be dispersed. Each layer-forming composition may be filtered by a known method before being subjected to the coating step. Filtration may be performed, for example, by filter filtration.The filter used for filtration may be, for example, a filter with a pore size of 0.01 to 3 μm (eg, a glass fiber filter, a polypropylene filter, etc.).

[0087] (Coating process) The non-magnetic layer and the magnetic layer can be formed by sequentially or simultaneously applying a non-magnetic layer forming composition and a magnetic layer forming composition in a multi-layer manner. The backcoat layer can be formed by applying a backcoat layer forming composition to the surface opposite to the surface of the non-magnetic support that has the non-magnetic layer and the magnetic layer (or the non-magnetic layer and / or the magnetic layer will be provided later). For details of the application for forming each layer, refer to paragraph 0066 of JP2010-231843A.

[0088] (Other processes) For other various steps for manufacturing a magnetic recording medium, for example, refer to paragraphs 0067 to 0070 of JP-A-2010-231843. For example, for the orientation treatment, the coating layer of the magnetic layer-forming composition can be subjected to the orientation treatment in the orientation zone while the coating layer is in a wet state. For the orientation treatment, various known techniques including those described in paragraph 0052 of JP-A-2010-24113 can be applied. For example, the vertical orientation treatment can be performed by a known method such as a method using magnets with opposite poles facing each other. In the orientation zone, the drying speed of the coating layer can be controlled by the temperature and volume of the drying air and / or the conveying speed in the orientation zone. In addition, the coating layer may be pre-dried before being conveyed to the orientation zone. As an example, the magnetic field strength in the vertical orientation treatment can be 0.10 to 0.80 T, or 0.10 to 0.60 T. In addition, a calendar treatment can be performed as a treatment for enhancing the surface smoothness of the magnetic recording medium. Regarding the conditions of the calendering, for example, the calender pressure (linear pressure) can be 200 to 500 kN / m, and preferably 250 to 350 kN / m, the calender temperature (surface temperature of the calender roll) can be, for example, 70 to 120° C., and preferably 80 to 100° C., and the calender speed can be, for example, 50 to 300 m / min, and preferably 50 to 200 m / min.

[0089] The magnetic recording medium according to one embodiment of the present invention may be a tape-shaped magnetic recording medium (magnetic tape) or a disk-shaped magnetic recording medium (magnetic disk). For example, a magnetic tape is usually housed in a magnetic tape cartridge, and the magnetic tape cartridge is mounted in a magnetic recording and reproducing device. A servo pattern may be formed on the magnetic recording medium by a known method to enable head tracking in the magnetic recording and reproducing device. "Formation of a servo pattern" may also be referred to as "recording of a servo signal." Formation of a servo pattern will be described below using a magnetic tape as an example.

[0090] The servo pattern is usually formed along the longitudinal direction of the magnetic tape. Control methods that use servo signals (servo control) include timing-based servo (TBS), amplitude servo, and frequency servo.

[0091] As shown in ECMA (European Computer Manufacturers Association)-319 (June 2001), magnetic tapes (generally called "LTO tapes") that comply with the LTO (Linear Tape-Open) specifications employ a timing-based servo system. In this timing-based servo system, a servo pattern is formed by a pair of non-parallel magnetic stripes (also called "servo stripes") that are continuously arranged in the longitudinal direction of the magnetic tape. As described above, the reason why the servo pattern is formed by a pair of non-parallel magnetic stripes is to inform the servo signal reading element that passes over the servo pattern of its passing position. Specifically, the pair of magnetic stripes is formed so that the interval between them changes continuously along the width direction of the magnetic tape, and the servo signal reading element can know the relative position between the servo pattern and the servo signal reading element by reading the interval. This relative position information enables tracking of the data track. For this purpose, a plurality of servo tracks are usually set on the servo pattern along the width direction of the magnetic tape.

[0092] A servo band is made up of a series of servo signals along the length of the magnetic tape. Usually, multiple servo bands are provided on a magnetic tape. For example, there are five servo bands on an LTO tape. The area between two adjacent servo bands is called a data band. A data band is made up of multiple data tracks, and each data track corresponds to one servo track.

[0093] Also, in one embodiment, as shown in JP 2004-318983 A, information indicating the number of the servo band (also called "servo band ID (identification)" or "UDIM (Unique Data Band Identification Method) information") is embedded in each servo band. This servo band ID is recorded by shifting a specific one of a plurality of pairs of servo stripes in the servo band so that its position is displaced relatively in the longitudinal direction of the magnetic tape. Specifically, the way in which a specific one of a plurality of pairs of servo stripes is shifted is changed for each servo band. As a result, the recorded servo band ID is unique for each servo band, so that the servo band can be uniquely identified simply by reading one servo band with a servo signal reading element.

[0094] Incidentally, there is also a method for uniquely identifying servo bands that uses the staggered method as shown in ECMA-319 (June 2001). In this staggered method, a group of pairs of non-parallel magnetic stripes (servo stripes) arranged continuously in the longitudinal direction of the magnetic tape are recorded so that they are shifted in the longitudinal direction of the magnetic tape for each servo band. The combination of the shift between adjacent servo bands is unique across the entire magnetic tape, so when the servo pattern is read by two servo signal reading elements, it is possible to uniquely identify the servo bands.

[0095] Also, as specified in ECMA-319 (June 2001), information indicating the longitudinal position of the magnetic tape (also called "LPOS (Longitudinal Position) information") is usually embedded in each servo band. Like UDIM information, this LPOS information is also recorded by shifting the positions of a pair of servo stripes in the longitudinal direction of the magnetic tape. However, unlike UDIM information, the same signal is recorded in each servo band with this LPOS information.

[0096] It is also possible to embed information other than the above UDIM information and LPOS information in the servo bands. In this case, the embedded information may be different for each servo band, such as UDIM information, or may be common to all servo bands, such as LPOS information. Also, methods other than those described above can be used to embed information in the servo bands. For example, a predetermined code may be recorded by thinning out a predetermined pair from a group of pairs of servo stripes.

[0097] The head for forming a servo pattern is called a servo write head. The servo write head has a pair of gaps corresponding to the pair of magnetic stripes, the number of which is equal to the number of servo bands. Usually, a core and a coil are connected to each pair of gaps, and a magnetic field generated in the core can generate a leakage magnetic field in the pair of gaps by supplying a current pulse to the coil. When forming a servo pattern, a magnetic pattern corresponding to the pair of gaps can be transferred to the magnetic tape by inputting a current pulse while running the magnetic tape on the servo write head, thereby forming the servo pattern. The width of each gap can be appropriately set according to the density of the servo pattern to be formed. The width of each gap can be set, for example, to 1 μm or less, 1 to 10 μm, or 10 μm or more.

[0098] Before forming a servo pattern on the magnetic tape, the magnetic tape is usually subjected to a demagnetization (erase) process. This erase process can be performed by applying a uniform magnetic field to the magnetic tape using a direct current magnet or an alternating current magnet. There are two types of erase processes: DC (Direct Current) erase and AC (Alternating Current) erase. AC erase is performed by gradually lowering the strength of the magnetic field applied to the magnetic tape while reversing the direction of the magnetic field. On the other hand, DC erase is performed by applying a unidirectional magnetic field to the magnetic tape. There are two more methods of DC erase. The first method is horizontal DC erase, which applies a unidirectional magnetic field along the longitudinal direction of the magnetic tape. The second method is vertical DC erase, which applies a unidirectional magnetic field along the thickness direction of the magnetic tape. The erase process may be performed on the entire magnetic tape, or may be performed for each servo band of the magnetic tape.

[0099] The direction of the magnetic field of the formed servo pattern is determined according to the direction of erasure. For example, when the magnetic tape is subjected to horizontal DC erasure, the servo pattern is formed so that the direction of the magnetic field is opposite to the direction of erasure. This can increase the output of the servo signal obtained by reading the servo pattern. As shown in JP2012-53940A, when the magnetic pattern is transferred to the magnetic tape that has been vertically DC erased using the above gap, the servo signal obtained by reading the formed servo pattern has a unipolar pulse shape. On the other hand, when the magnetic pattern is transferred to the magnetic tape that has been horizontally DC erased using the above gap, the servo signal obtained by reading the formed servo pattern has a bipolar pulse shape.

[0100] The magnetic tape is usually contained in a magnetic tape cartridge, and the magnetic tape cartridge is loaded into a magnetic recording and reproducing device.

[0101] [Magnetic tape cartridge] One aspect of the present invention relates to a magnetic tape cartridge including the above-mentioned magnetic recording medium in tape form (that is, a magnetic tape).

[0102] The details of the magnetic tape contained in the magnetic tape cartridge are as described above.

[0103] In a magnetic tape cartridge, the magnetic tape is generally accommodated inside the cartridge body in a state where it is wound around a reel. The reel is provided rotatably inside the cartridge body. As the magnetic tape cartridge, a single-reel type magnetic tape cartridge having one reel inside the cartridge body and a twin-reel type magnetic tape cartridge having two reels inside the cartridge body are widely used. When a single-reel type magnetic tape cartridge is loaded into a magnetic recording and reproducing device for recording and / or reproducing data on the magnetic tape, the magnetic tape is pulled out from the magnetic tape cartridge and wound around the reel on the magnetic recording and reproducing device side. A magnetic head is disposed on the magnetic tape transport path from the magnetic tape cartridge to the take-up reel. The magnetic tape is fed and wound between the reel (supply reel) on the magnetic tape cartridge side and the reel (take-up reel) on the magnetic recording and reproducing device side. During this time, the magnetic head comes into contact with and slides on the surface of the magnetic layer side of the magnetic tape, thereby recording and / or reproducing data. In contrast, a dual-reel magnetic tape cartridge has both a supply reel and a take-up reel inside the magnetic tape cartridge. The magnetic tape cartridge may be either a single-reel or dual-reel magnetic tape cartridge. The magnetic tape cartridge may include the magnetic tape according to one aspect of the present invention, and other aspects may be based on known techniques.

[0104] [Magnetic recording and playback device] One aspect of the present invention relates to a magnetic recording and reproducing device including the above magnetic recording medium.

[0105] In the present invention and this specification, the term "magnetic recording and reproducing device" refers to a device capable of at least one of recording data to a magnetic recording medium and reproducing data recorded on the magnetic recording medium. Such a device is generally called a drive. The magnetic recording and reproducing device may be, for example, a sliding type magnetic recording and reproducing device. The sliding type magnetic recording and reproducing device refers to a device in which the surface of the magnetic layer and a magnetic head come into contact and slide when recording data on the magnetic recording medium and / or reproducing the recorded data. For example, the magnetic recording and reproducing device may include the magnetic tape cartridge in a removable manner.

[0106] The magnetic recording and reproducing device may include a magnetic head. The magnetic head may be a recording head capable of recording data on a magnetic recording medium, or may be a reproducing head capable of reproducing data recorded on the magnetic recording medium. In one embodiment, the magnetic recording and reproducing device may include both a recording head and a reproducing head as separate magnetic heads. In another embodiment, the magnetic head included in the magnetic recording and reproducing device may have a configuration in which both an element for recording data (recording element) and an element for reproducing data (reproducing element) are provided in one magnetic head. Hereinafter, the element for recording data and the element for reproducing data are collectively referred to as "data element". As the reproducing head, a magnetic head (MR head) including a magnetoresistive (MR) element capable of reading data recorded on a magnetic recording medium with good sensitivity as a reproducing element is preferable. As the MR head, various known MR heads such as an anisotropic magnetoresistive (AMR) head, a giant magnetoresistive (GMR) head, and a tunnel magnetoresistive (TMR) head may be used. Also, the magnetic head that records and / or reproduces data may include a servo signal read element. Alternatively, the magnetic recording and reproducing device may include a magnetic head (servo head) equipped with a servo signal read element as a head separate from the magnetic head that records and / or reproduces data. For example, a magnetic head that records and / or reproduces recorded data (hereinafter also referred to as a "recording and reproducing head") may include two servo signal read elements, and each of the two servo signal read elements can simultaneously read two adjacent servo bands. One or more data elements may be disposed between the two servo signal read elements.

[0107] In the magnetic recording and reproducing device, data can be recorded on the magnetic recording medium and / or data recorded on the magnetic recording medium can be reproduced by contacting and sliding the magnetic head against the surface of the magnetic recording medium on the magnetic layer side. The magnetic recording and reproducing device may include the magnetic recording medium according to one embodiment of the present invention, and other known techniques may be applied.

[0108] For example, when recording data and / or reproducing recorded data, tracking using servo signals is first performed. That is, the servo signal reading element is made to follow a specific servo track, so that the data element passes over the target data track. The data track is moved by changing the servo track read by the servo signal reading element in the tape width direction. The recording / reproducing head can also record and / or reproduce data on other data bands by using the UDIM information described above to move the servo signal reading element to a specific servo band and start tracking on that servo band. EXAMPLES

[0109] The present invention will be described below based on examples. However, the present invention is not limited to the embodiments shown in the examples. The "parts" and "%" described below are based on mass. In addition, the steps and evaluations described below were performed in an environment with an atmospheric temperature of 23°C ± 1°C unless otherwise specified.

[0110] In the examples and comparative examples, polyurethane resin A used in preparing the nonmagnetic layer-forming composition is a polyurethane resin having an aromatic cyclic structure that was synthesized by the following method.

[0111] [Synthesis of polyurethane resin A having an aromatic ring structure] Polyester polyol (a) shown in Table 2, HPN (2,2-dimethyl-1,3-propanediol mono (hydroxypivalate)) as a short chain diol and compound (b) which is an EO (ethylene oxide) adduct of Na sulfoisophthalic acid were dissolved in a cyclohexanone 30% solution at a liquid temperature of 60 ° C. under a nitrogen gas flow in a container equipped with a reflux condenser and a stirrer and previously substituted with nitrogen. Next, 60 ppm (mass basis) of dibutyltin dilaurate was added as a catalyst and dissolved for another 15 minutes. Furthermore, MDI (4,4-diphenylmethane diisocyanate) was added as a diisocyanate, and the mixture was heated and reacted at a liquid temperature of 90 ° C. for 6 hours to obtain polyurethane resin A. The raw material composition ratio was the value shown in Table 1.

[0112] [Table 1]

[0113] [ka]

[0114] [ka]

[0115] [ka]

[0116] [Table 2]

[0117] The number average molecular weight of the polyester polyol (a) shown in Table 2 is a value calculated from the hydroxyl value measured by the method described in JIS standard K1557-1:2007.

[0118] [ka]

[0119] The weight average molecular weight of polyurethane resin A, determined by the method described above, was 67,000.

[0120] The content of metal sulfonate base (SO3Na) in polyurethane resin A was calculated from the concentration of Na, a metal component, using the following formula, and was found to be 70 eq / ton. In the formula, "23" is the atomic weight of Na. The Na concentration (unit: ppm (by mass)) was determined by atomic absorption spectrometry after carbonizing 0.1 g of the sample and dissolving it in acid. Metal sulfonate base (SO3Na) content (eq / ton) = Na concentration (ppm) / 23

[0121] Polyurethane resin A was analyzed in chloroform-d solvent using a Varian Gemini-200 nuclear magnetic resonance analyzer (NMR). 1 H-NMR analysis was performed to determine the polyurethane composition by its integral ratio. 1 The urethane group concentration was calculated from the mole percent of isocyanate determined by H-NMR analysis using the following formula: The calculated urethane group concentration was 3.5 meq / g. Urethane group concentration (meq / g) = 10 3 × {2 × mole % of isocyanate × (1 / 100)} / unit molecular weight of polyurethane)

[0122] [Example 1] <Formulation of the composition for forming the magnetic layer> (Magnetic liquid) Hexagonal barium ferrite powder: 100.0 parts (Average particle size: 17 nm, activation volume: 1300 nm 3 ) Oleic acid: 1.5 parts Vinyl chloride resin: 10.0 parts (Kaneka MR-104) Polyurethane resin: 4.0 parts (Toyobo UR-4800 (sulfonic acid group-containing polyester polyurethane resin)) Methyl ethyl ketone: 300.0 parts Cyclohexanone: 300.0 parts (abrasive liquid) Alumina powder (specific surface area 19m 2 / g α-alumina): 9.0 parts Vinyl chloride resin: 0.7 parts (Kaneka MR-110) Cyclohexanone: 20.0 parts (Protrusion forming agent liquid) Silica colloid particles (colloidal silica) (average particle size: 150 nm): 2.0 parts Methyl ethyl ketone: 8.0 parts (Other Ingredients) Stearic acid: 1.0 parts Stearic acid amide: 0.3 parts Butyl stearate: 1.5 parts Methyl ethyl ketone: 110.0 parts Cyclohexanone: 110.0 parts Polyisocyanate (Tosoh Coronate L): 2.5 parts

[0123] <Formulation of the composition for forming the nonmagnetic layer> Carbon black: see Table 3 (Specific surface area: see Table 3, pH: see Table 3) Oleic acid: 4.0 parts Polyurethane resin A: See Table 3 Methyl ethyl ketone: 510.0 parts Cyclohexanone: 200.0 parts Stearic acid: 1.5 parts Stearic acid amide: 0.3 parts Butyl stearate: 1.5 parts

[0124] <Formulation of the composition for forming the backcoat layer> Carbon black: 100.0 parts (Average particle size: 40nm, DBP (Dibutyl phthalate) oil absorption: 74cm 3 / 100g) Copper phthalocyanine: 3.0 parts Nitrocellulose: 25.0 parts Polyurethane resin: 60.0 parts (Toyobo UR-8401 (sulfonic acid group-containing polyester polyurethane resin)) Polyester resin: 4.0 parts (Byron 500 manufactured by Toyobo) Alumina powder (specific surface area 17m 2 / g α-alumina): 1.0 parts Polyisocyanate: 15.0 parts (Tosoh Coronate L) Methyl ethyl ketone: 600.0 parts Toluene: 600.0 parts

[0125] <Preparation of compositions for forming each layer> A magnetic layer forming composition was prepared as follows. The components of the magnetic liquid were mixed and diluted using an open kneader, and then dispersed in a horizontal bead mill disperser for 30 passes using zirconia (ZrO2) beads (hereinafter referred to as "Zr beads") with a particle size of 0.1 mm, with a bead filling rate of 80 volume%, a rotor tip speed of 10 m / sec, and a residence time of 2 minutes per pass. For the abrasive liquid, a mixture of the components of the abrasive liquid described above (alumina powder, polyvinyl chloride resin, and cyclohexanone) was prepared, and then this mixture was placed in a horizontal bead mill disperser together with Zr beads having a particle size of 0.3 mm, and the bead volume / (abrasive liquid volume+bead volume) was adjusted to 80 volume %. The bead mill dispersion process was carried out for 120 minutes, and the processed liquid was removed and subjected to ultrasonic dispersion filtration using a flow-type ultrasonic dispersion filtration device. The magnetic liquid, abrasive liquid, protrusion-forming agent liquid and other components were introduced into a dissolver mixer and stirred for 30 minutes at a peripheral speed of 10 m / sec. After that, the mixture was processed three times using a flow-type ultrasonic disperser at a flow rate of 7.5 kg / min, and then filtered through a 1 μm filter to prepare a composition for forming a magnetic layer.

[0126] A composition for forming a nonmagnetic layer was prepared as follows. The above components, except for the lubricants (stearic acid, stearic acid amide, and butyl stearate), were kneaded and diluted using an open kneader, and then dispersed using a horizontal bead mill disperser.Then, the lubricants (stearic acid, stearic acid amide, and butyl stearate) and methyl ethyl ketone for adjusting the coating thickness were added, and the mixture was stirred and mixed using a dissolver stirrer to prepare a composition for forming a nonmagnetic layer. In Example 1, as well as Examples 2 to 8 and Comparative Examples 1 to 3 described below, when preparing the composition for forming the nonmagnetic layer, methyl ethyl ketone for adjusting the coating thickness was used in an amount in the range of 70.0 to 510.0 parts by mass per 100.0 parts by mass of the nonmagnetic powder used to prepare the composition for forming the nonmagnetic layer.

[0127] A composition for forming a backcoat layer was prepared as follows. The above components except for the polyisocyanate were introduced into a dissolver mixer and stirred at a peripheral speed of 10 m / sec for 30 minutes, and then dispersed using a horizontal bead mill disperser. Then, the polyisocyanate was added, and the mixture was stirred and mixed using the dissolver mixer to prepare a composition for forming a backcoat layer.

[0128] <Magnetic tape production> A non-magnetic layer was formed by applying a non-magnetic layer forming composition to one surface of a 6.0 μm-thick biaxially oriented polyethylene naphthalate support to a thickness shown in Table 4 and drying the composition. A coating layer was formed by applying the magnetic layer forming composition prepared above to a thickness shown in Table 4 on the formed non-magnetic layer. While the coating layer of the magnetic layer forming composition was in a wet (undried) state, a vertical orientation treatment was performed in which a magnetic field with a magnetic field strength of 0.15 T was applied perpendicularly to the surface of the coating layer. The coating layer was then dried to form a magnetic layer. Then, a backcoat layer forming composition was applied to the surface of the support opposite to the surface on which the non-magnetic layer and magnetic layer were formed, and dried to a thickness of 0.5 μm after drying. Then, a calendering process was performed using a calendering machine consisting of only metal rolls at a speed of 100 m / min, a linear pressure of 294 kN / m, and a calendering temperature of 100° C. Then, a heat treatment was performed for 36 hours in an atmosphere at a temperature of 70° C. After the heat treatment, the film was slit into a 1 / 2 inch width (1 inch = 0.0254 meters) to obtain a magnetic tape.

[0129] [Examples 2 to 8, Comparative Examples 1 to 3] A magnetic tape was produced by the method described for Example 1, except that the items shown in the table below were changed as shown in the table below. The thickness of the nonmagnetic layer was adjusted by the amount of methyl ethyl ketone used to adjust the coating thickness when preparing the nonmagnetic layer forming composition. The thickness of the magnetic layer was adjusted by the amount of the magnetic layer forming composition applied. In the examples and comparative examples in which vinyl chloride resin was used as the binder for the nonmagnetic layer, MR-104 manufactured by Kaneka Corporation was used as the vinyl chloride resin. Comparative Example 1 is a comparative example conforming to Example 1 of JP 2020-144960 A (Patent Document 1), and Comparative Example 3 is a comparative example conforming to Example 10 of JP 2005-267714 A (Patent Document 3).

[0130] [Evaluation method] <Chlorine content (magnetic layer + non-magnetic layer), iron content (magnetic layer + non-magnetic layer)> For each of the magnetic tapes of the Examples and Comparative Examples, the chlorine content (magnetic layer + non-magnetic layer) and iron content (magnetic layer + non-magnetic layer) were determined by the method described above.

[0131] <Porosity and thicknesses of non-magnetic layers> A sample for cross-sectional observation was prepared by the method described above as a specific example. Using the prepared sample for cross-sectional observation, the void ratio of the nonmagnetic layer and the thickness of the magnetic layer were determined by the method described above. The thickness of the nonmagnetic layer was also determined by the method described above as a method for measuring the thickness of the magnetic layer. A Hitachi FE-SEM S4800 was used as a field emission scanning electron microscope (FE-SEM) for SEM observation.

[0132] <Magnetic layer Bm> For each of the magnetic tapes in the Examples and Comparative Examples, a vibrating sample magnetometer (manufactured by Toyo Kogyo) was used to sweep and measure an external magnetic field on the magnetic tape at a maximum external magnetic field of 15 kOe and a scan speed of 60 Oe / sec at a measurement temperature of 23°C ± 1°C to determine the magnetization amount Φm [G μm]. The magnetic layer Bm was calculated as the value obtained by dividing Φm [G·μm] by the magnetic layer thickness (unit: μm) obtained above. The magnetic layer Bm is preferably 1000 G (gauss) or more, more preferably 1100 G or more, 1200 G or more, and 1300 G or more in that order. The higher the magnetic layer Bm, the more preferable it is from the viewpoint of improving electromagnetic conversion characteristics. In one embodiment, the magnetic layer Bm can be, for example, 3000 G or less, 2500 G or less, or 2000 G or less.

[0133] <Electromagnetic conversion characteristics (SNR: Signal-to-Noise ratio)> For each of the magnetic tapes of the examples and comparative examples, the SNR was measured by a 1 / 2 inch reel tester with a fixed head under an environment of a temperature of 23°C and a relative humidity of 50%. The magnetic head / magnetic tape relative speed was 6 m / sec. A MIG (Metal-In-Gap) head (gap length 0.15 μm, track width 1.0 μm, 1.8 T) was used for recording, and the recording current was set to the optimum recording current for each magnetic tape. A GMR head with an element thickness of 15 nm, a shield interval of 0.1 μm, and a track width of 1.0 μm was used as the reproducing head. A signal with a linear recording density (325 kfci) was recorded, and the reproducing signal was measured with a spectrum analyzer manufactured by Shibasoku Co., Ltd. The ratio of the output of the carrier signal to the integrated noise of the entire spectrum band was taken as the SNR, and was calculated as a relative value when Comparative Example 1 was taken as the reference (0.0 dB). The unit kfci is the unit of linear recording density (not convertible to SI units). The signal used was the portion where the signal had stabilized sufficiently after the magnetic tape had started to run.

[0134] <ΔSNR> After the evaluation of the electromagnetic conversion characteristics, the magnetic tape was stored for two weeks in an environment with an atmospheric temperature of 60° C. and a relative humidity of 90%, and then the SNR was measured by the above method. ΔSNR was calculated by the following formula. ΔSNR = SNR measured after storage - SNR measured before storage

[0135] The results are shown in the table below.

[0136] [Table 3]

[0137] [Table 4]

[0138] From the results shown in Table 4, it can be confirmed that in the magnetic tapes of Examples 1 to 8, there is little deterioration in the electromagnetic conversion characteristics after storage under harsh conditions. [Industrial Applicability]

[0139] The present invention is useful in the technical fields of various magnetic recording media such as magnetic tapes for data storage.

Claims

1. A non-magnetic support and a magnetic layer containing ferromagnetic powder, a non-magnetic layer containing a non-magnetic powder between the non-magnetic support and the magnetic layer, The total chlorine content of the magnetic layer and the non-magnetic layer is 30.0 mg / m 2 is less than or equal to, and The total iron content of the magnetic layer and the non-magnetic layer is 300.0 mg / m 2 1. A magnetic recording medium comprising:

2. 2. The magnetic recording medium according to claim 1, wherein in a cross-sectional image taken by a scanning electron microscope, the void ratio of the nonmagnetic layer is 10.0% or less.

3. The magnetic recording medium according to claim 1 , wherein the non-magnetic powder in the non-magnetic layer contains carbon black.

4. 4. The magnetic recording medium according to claim 3, wherein the non-magnetic layer contains 50.0% by mass or more of carbon black based on the total amount of the non-magnetic powder.

5. 2. The magnetic recording medium according to claim 1, wherein the nonmagnetic layer has a thickness of 1.00 [mu]m or less.

6. 2. The magnetic recording medium according to claim 1, further comprising a backcoat layer containing a nonmagnetic powder on the surface of said nonmagnetic support opposite to the surface having said nonmagnetic layer and said magnetic layer.

7. 2. The magnetic recording medium according to claim 1, which is a magnetic tape.

8. In a cross-sectional image taken by a scanning electron microscope, the porosity of the nonmagnetic layer is 10.0% or less, the non-magnetic layer contains 50.0% by mass or more of carbon black based on the total amount of the non-magnetic powder, The thickness of the nonmagnetic layer is 1.00 μm or less, a backcoat layer containing a nonmagnetic powder on the surface side of the nonmagnetic support opposite to the surface side having the nonmagnetic layer and the magnetic layer; and 2. The magnetic recording medium according to claim 1, which is a magnetic tape.

9. A magnetic tape cartridge comprising the magnetic tape according to claim 7 or 8.

10. A magnetic recording and reproducing device comprising the magnetic recording medium according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Magnetic recording medium

    JP2004103067A

  • Magnetic recording medium

    JP2005267714A

  • Magnetic recording medium and magnetic recording reproducing device

    JP2020144960A